Solid electrolyte composition, electrode composition, method for manufacturing solid electrolyte sheet, method for manufacturing electrode sheet, and method for manufacturing battery

A solid electrolyte composition with specific nitrogen-containing organic substances and styrene elastomers enhances fluidity and dispersion stability, enabling efficient manufacturing of solid electrolyte sheets and electrodes, thus improving the production of all-solid secondary batteries.

CN119213513APending Publication Date: 2024-12-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041397.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing solid electrolyte compositions face challenges in achieving a balance between fluidity and dispersion stability, which are essential for the development of a new electrolyte compositions, which are not adequately addressed by existing technologies, leading to inefficiencies in the manufacturing of solid electrolyte sheets and electrodes.

Method used

A solid electrolyte composition comprising a solvent, a solid electrolyte, a binder, and a nitrogen-containing organic substance, such as a styrene elastomer, with specific ratios and properties to improve fluidity and dispersion stability, utilizing styrene elastomers, and specific nitrogen-containing organic substances, and a solvent with a boiling point between 100°C and 250°C, to enhance the fluidity and dispersion stability of the electrolyte.

Benefits of technology

The composition allows for the efficient and uniform application of solid electrolyte sheets and electrodes over large areas, improving the manufacturing efficiency and performance of all-solid secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213513A_ABST
    Figure CN119213513A_ABST
Patent Text Reader

Abstract

This solid electrolyte composition is provided with a solvent and an ion conductor that contains a solid electrolyte, a binder, and a nitrogen-containing organic material and is dispersed in the solvent, the solid electrolyte containing a sulfide solid electrolyte, the binder containing a styrene-based elastomer, and the nitrogen-containing organic material containing a nitrogen-containing organic material. The nitrogen-containing organic compound contains at least one compound selected from the group consisting of a primary amine, a secondary amine, an aminohydroxy compound, and a diamine, and each of the primary amine, the secondary amine, the aminohydroxy compound, and the diamine has at least one compound selected from the group consisting of a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms. The ratio of the mass of the nitrogen-containing organic material to the mass of the solid electrolyte is 0.30 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte composition, an electrode composition, a method for producing a solid electrolyte sheet, a method for producing an electrode sheet, and a method for producing a battery. Background Art

[0002] Patent Document 1 states that at least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer contains a dispersant, wherein the dispersant is a compound having a functional group such as a group containing a basic nitrogen atom, and an alkyl group having 8 or more carbon atoms or an aryl group having 10 or more carbon atoms.

[0003] Patent Document 2 describes an electronic material including a compound having an imidazoline ring and an aromatic ring and having a molecular weight of less than 350.

[0004] Patent Document 3 describes a method for manufacturing a lithium secondary battery in which a solid electrolyte layer is formed by applying a solid electrolyte-forming composition containing a solid electrolyte and a specific compound to a substrate, etc., and drying the composition. As the specific compound, for example, 1-hydroxyethyl-2-enyl imidazoline is described.

[0005] Prior Art Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-212990

[0007] Patent Document 2: International Publication No. 2020 / 136975

[0008] Patent Document 3: Japanese Patent Application Publication No. 2020-161364 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the prior art, a technology for improving the fluidity and dispersion stability of a solid electrolyte composition is desired.

[0011] Means for solving problems

[0012] A solid electrolyte composition according to one embodiment of the present disclosure comprises a solvent and an ion conductor.

[0013] The ion conductor comprises a solid electrolyte, a binder and a nitrogen-containing organic substance, and is dispersed in the solvent.

[0014] The solid electrolyte comprises a sulfide solid electrolyte,

[0015] The adhesive comprises a styrene elastomer,

[0016] The nitrogen-containing organic matter comprises at least one selected from primary amines, secondary amines, aminohydroxy compounds and diamines,

[0017] The primary amine, the secondary amine, the aminohydroxy compound and the diamine each have at least one selected from a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms,

[0018] The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.30 mass % or more.

[0019] Effects of the Invention

[0020] According to the present disclosure, it is possible to provide a solid electrolyte composition having improved fluidity and dispersion stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the solid electrolyte composition in Embodiment 1.

[0022] Figure 2 This is a graph for explaining a method for evaluating the fluidity of a solid electrolyte composition.

[0023] Figure 3 Schematic diagram of an electrode composition in Embodiment 2.

[0024] Figure 4 This is a flowchart showing a method for producing a solid electrolyte sheet in the third embodiment.

[0025] Figure 5 This is a cross-sectional view of an electrode assembly in the third embodiment.

[0026] Figure 6 This is a cross-sectional view of a transfer sheet in Embodiment 3.

[0027] Figure 7 This is a cross-sectional view of an electrode in the fourth embodiment.

[0028] Figure 8 This is a cross-sectional view of an electrode transfer sheet in the fourth embodiment.

[0029] Fig. 9 This is a cross-sectional view of a battery precursor in the fourth embodiment.

[0030] Fig.10 This is a cross-sectional view of a battery in Embodiment 5. DETAILED DESCRIPTION

[0031] (Insights that form the basis of this disclosure)

[0032] In the field of secondary batteries in the past, organic electrolytes obtained by dissolving electrolyte salts in organic solvents were mainly used as electrolytes. In secondary batteries using organic electrolytes, there is a concern about leakage. It is also pointed out that the heat generated in the event of a short circuit is large.

[0033] On the other hand, all-solid secondary batteries that use inorganic solid electrolytes instead of organic electrolytes are attracting attention. All-solid secondary batteries do not cause leakage. Inorganic solid electrolytes have high thermal stability, so it is expected that they can suppress heat generation in the event of a short circuit.

[0034] However, in order to put all-solid secondary batteries using solid electrolytes into practical use, it is necessary to prepare a solid electrolyte composition containing a solid electrolyte and having fluidity. For example, by using a solid electrolyte composition having fluidity, a solid electrolyte composition can be applied to the surface of an electrode to form a solid electrolyte sheet. The solid electrolyte sheet, for example, serves as a battery separator.

[0035] In order to manufacture the solid electrolyte sheet used for the diaphragm in a large area and efficiently, it is necessary to use a coating device such as a die coater to apply the solid electrolyte composition. At this time, it is necessary to suppress the sedimentation of the particles in the solid electrolyte composition, that is, it is necessary to improve the dispersion stability of the solid electrolyte composition. Thus, the uniformity of the thickness direction of the solid electrolyte sheet is improved. In addition, even when the solid electrolyte composition is applied for a long time, a coating film with excellent uniformity can be continuously manufactured. On the other hand, in order to improve the uniformity of the film thickness in the width direction and the uniformity of the film thickness in the length direction of the solid electrolyte sheet, it is necessary to improve the fluidity of the solid electrolyte composition. As described above, a solid electrolyte composition with improved fluidity and dispersion stability is required.

[0036] On the other hand, in order to make all-solid secondary batteries using solid electrolytes practical, it is necessary to prepare an electrode composition with fluidity by adding active materials to the above-mentioned solid electrolyte composition. For example, by applying the electrode composition on the surface of the collector and drying it, electrodes, i.e., positive and negative electrodes, can be made. In order to manufacture positive and negative electrodes over a large area and with high efficiency, an electrode composition with improved fluidity and dispersion stability is required, as with the solid electrolyte composition.

[0037] The solid electrolyte composition, for example, comprises a solid electrolyte, a binder and a dispersant. In the solid electrolyte composition, the dispersibility of the solid electrolyte is generally improved by adding a dispersant to the solid electrolyte. In the case of using a sulfide solid electrolyte as the solid electrolyte, the dispersibility of the sulfide solid electrolyte is improved by using a nitrogen-containing organic matter as a dispersant. On the other hand, in this case, in the solid electrolyte composition, the surface area of ​​the solid electrolyte increases, so a strong interaction may occur between the solid electrolytes. As a result, the fluidity and dispersion stability of the solid electrolyte composition are significantly impaired. Therefore, in order to mitigate the strong interaction between the solid electrolytes, it is important to appropriately adjust the interaction between the solid electrolyte, the binder and the dispersant.

[0038] In order to prepare a solid electrolyte composition, it is necessary to mix a solid electrolyte, an organic solvent, a binder and a dispersant. The inventors prepared a solid electrolyte composition comprising these materials, and studied the dispersion stability of the solid electrolyte and the fluidity of the solid electrolyte composition. As a result, the inventors found that by containing specific materials, the fluidity and dispersion stability of the solid electrolyte composition can be improved. Based on the above perspectives, the technical composition of the present disclosure is conceived.

[0039] (Summary of a technical solution involved in the present disclosure)

[0040] The solid electrolyte composition according to the first aspect of the present disclosure comprises a solvent and an ion conductor.

[0041] The ion conductor comprises a solid electrolyte, a binder and a nitrogen-containing organic substance, and is dispersed in the solvent.

[0042] The solid electrolyte comprises a sulfide solid electrolyte,

[0043] The adhesive comprises a styrene elastomer,

[0044] The nitrogen-containing organic matter comprises at least one selected from primary amines, secondary amines, aminohydroxy compounds and diamines,

[0045] The primary amine, the secondary amine, the aminohydroxy compound and the diamine each have at least one selected from a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms,

[0046] The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.30 mass % or more.

[0047] According to the first invention, a solid electrolyte composition having improved fluidity and dispersion stability can be provided. In addition, by using a solid electrolyte composition having improved fluidity and dispersion stability, a solid electrolyte sheet and a battery can be manufactured in a large area and with high efficiency.

[0048] The second technical solution of the present disclosure, for example, can be set on the basis of the solid electrolyte composition of the first technical solution: the ratio η1 / η2 of the viscosity η1 of the solid electrolyte composition measured at 25°C and a shear rate of 1 / second to the viscosity η2 of the solid electrolyte composition measured at 25°C and a shear rate of 100 / second is greater than 1.4.

[0049] According to the second invention, a solid electrolyte composition having further improved dispersion stability can be provided. In addition, the solid electrolyte composition can be easily applied to a substrate.

[0050] According to a third aspect of the present disclosure, in the solid electrolyte composition according to the first or second aspect, for example, the styrene-based elastomer may include styrene-butadiene rubber.

[0051] According to the third invention, since styrene-butadiene rubber is excellent in flexibility and elasticity and excellent in filling properties during heat compression, it is particularly suitable as a binder for a solid electrolyte sheet.

[0052] A fourth aspect of the present disclosure may be, for example, the solid electrolyte composition of the first or second aspect, wherein the styrene-based elastomer includes a modified styrene-butadiene rubber and a modified styrene-ethylene / butylene-styrene block copolymer.

[0053] According to the fourth technical solution, since the modified styrene-butadiene rubber and the modified styrene-ethylene / butylene-styrene block copolymer can further improve the dispersibility of the solid electrolyte, they are particularly suitable as a binder for the solid electrolyte sheet.

[0054] A fifth aspect of the present disclosure may be, for example, the solid electrolyte composition of any one of the first to fourth aspects, wherein the boiling point of the solvent is 100° C. or higher and 250° C. or lower.

[0055] According to the fifth aspect, since the solvent is not easily volatilized at room temperature, a solid electrolyte composition having improved fluidity can be obtained.

[0056] According to a sixth aspect of the present disclosure, for example, in the solid electrolyte composition according to any one of the first to fifth aspects, the solvent may contain an aromatic hydrocarbon.

[0057] According to the sixth technical solution, there is a tendency that the binder has high solubility in aromatic hydrocarbons. In particular, styrene-based elastomers are easily soluble in aromatic hydrocarbons. Since styrene-based elastomers are easily soluble in aromatic hydrocarbons, the fluidity and dispersion stability of the solid electrolyte composition can be further improved.

[0058] According to a seventh aspect of the present disclosure, for example, in the solid electrolyte composition according to the sixth aspect, the solvent may include tetralin.

[0059] According to the seventh invention, tetralin has a relatively high boiling point. Tetralin can improve the fluidity and dispersion stability of the solid electrolyte composition and can also stably produce the solid electrolyte composition through a kneading process.

[0060] According to an eighth aspect of the present disclosure, in the solid electrolyte composition according to any one of the first to seventh aspects, for example, the nitrogen-containing organic substance may include a linear alkenyl group.

[0061] According to the eighth aspect, the fluidity of the solid electrolyte composition can be further improved.

[0062] A ninth technical aspect of the present disclosure may be, for example, the solid electrolyte composition according to the eighth technical aspect, further comprising oleylamine.

[0063] According to the ninth aspect, the fluidity of the solid electrolyte composition can be further improved. Furthermore, the decrease in the ion conductivity of the ion conductor can be suppressed, thereby improving the output characteristics of the battery.

[0064] According to a tenth aspect of the present disclosure, for example, in the solid electrolyte composition according to any one of the first to ninth aspects, the nitrogen-containing compound may have an iodine value of 15 or more.

[0065] According to the tenth invention, the fluidity of the solid electrolyte composition can be further improved.

[0066] According to an eleventh aspect of the present disclosure, for example, in the solid electrolyte composition according to any one of the first to tenth aspects, the nitrogen-containing organic substance may include the aminohydroxy compound.

[0067] According to the eleventh invention, the fluidity of the solid electrolyte composition can be further improved.

[0068] The electrode composition according to the twelfth invention of the present disclosure comprises the solid electrolyte composition according to any one of the first to eleventh inventions and an active material.

[0069] According to the twelfth invention, an electrode composition having improved fluidity and dispersion stability can be provided. In addition, by using an electrode composition having improved fluidity and dispersion stability, an electrode sheet and a battery can be manufactured in a large area and with high efficiency.

[0070] A thirteenth technical solution of the present disclosure may be, for example, the electrode composition according to the twelfth technical solution, wherein the nitrogen-containing organic substance includes the aminohydroxy compound.

[0071] According to the thirteenth aspect, the fluidity of the electrode composition can be further improved. In addition, in the electrode composition, in addition to the dispersibility of the sulfide solid electrolyte, the dispersibility of the active material can also be further improved.

[0072] A method for manufacturing a solid electrolyte sheet according to a fourteenth technical solution of the present disclosure includes:

[0073] Applying the solid electrolyte composition of any one of the first to eleventh technical solutions on an electrode or a substrate to form a coating film; and

[0074] The solvent is removed from the coating film.

[0075] According to the fourteenth invention, a solid electrolyte sheet having a homogeneous quality and a uniform thickness can be manufactured over a large area and with high efficiency.

[0076] A fifteenth aspect of the present disclosure provides a method for manufacturing a battery comprising a first electrode, an electrolyte layer, and a second electrode in this order, and includes the following (i) or (ii).

[0077] (i) applying the solid electrolyte composition of any one of the first to eleventh embodiments on the first electrode to form a coating film;

[0078] removing the solvent from the coating film to form an electrode assembly including the first electrode and the electrolyte layer; and

[0079] The electrode assembly and the second electrode are combined such that the electrolyte layer is located between the first electrode and the second electrode.

[0080] (ii) coating the solid electrolyte composition of any one of the first to eleventh embodiments on a substrate to form a coating film;

[0081] removing the solvent from the coating film to form the electrolyte layer; and

[0082] The first electrode, the second electrode, and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode.

[0083] According to the fifteenth technical solution, a high-performance battery can be manufactured over a large area and with high efficiency.

[0084] The 16th technical solution of the present disclosure relates to a method for manufacturing an electrode sheet, comprising:

[0085] The electrode composition of the twelfth or thirteenth technical solution is applied on a current collector, a substrate or an electrode assembly to form a coating film; and

[0086] The solvent is removed from the coating film.

[0087] According to the sixteenth technical solution, it is possible to manufacture a homogeneous electrode sheet having a uniform thickness over a large area and with high efficiency.

[0088] The seventeenth invention of the present disclosure relates to a method for manufacturing a battery comprising a first electrode, an electrolyte layer, and a second electrode in this order, and includes the following (iii) or (iv) or (v).

[0089] (iii) coating the electrode composition of the twelfth or thirteenth technical solution on a current collector to form a coating film;

[0090] removing the solvent from the coating film to form the first electrode; and

[0091] The first electrode, the second electrode, and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode.

[0092] (iv) coating the electrode composition of the twelfth or thirteenth technical solution on a substrate to form a coating film;

[0093] removing the solvent from the coating film to form an electrode sheet for the first electrode; and

[0094] The first electrode, the second electrode, and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode.

[0095] (v) applying the electrode composition of the twelfth or thirteenth aspect to form a coating film on the electrolyte layer of the electrode assembly which is a stack of the first electrode and the electrolyte layer; and

[0096] The solvent is removed from the coating film to form an electrode sheet for a second electrode.

[0097] According to the seventeenth technical solution, a high-performance battery can be manufactured over a large area and with high efficiency.

[0098] The eighteenth technical solution of the present disclosure is a method for manufacturing a battery comprising a first electrode, an electrolyte layer, and a second electrode in this order, and includes (vi) or (vii).

[0099] (vi) coating the electrode composition of the twelfth or thirteenth technical solution on a current collector to form a first coating film;

[0100] removing the solvent from the first coating film to form the first electrode;

[0101] Applying the solid electrolyte composition of any one of the first to eleventh technical solutions on the first electrode to form a second coating film;

[0102] removing the solvent from the second coating film to form the electrolyte layer; and

[0103] The first electrode, the electrolyte layer, and the second electrode are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode.

[0104] (vii) coating the electrode composition of the twelfth or thirteenth technical solution on a first substrate to form a first coating film;

[0105] removing the solvent from the first coating film to form the first electrode;

[0106] The solid electrolyte composition of any one of the first to eleventh technical solutions is applied on a second substrate to form a second coating film;

[0107] removing the solvent from the second coating film to form the electrolyte layer; and

[0108] The first electrode, the second electrode, and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode.

[0109] According to the eighteenth technical solution, a high-performance battery can be manufactured over a large area and with high efficiency.

[0110] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0111] (Implementation Method 1)

[0112] Figure 11 is a schematic diagram of a solid electrolyte composition 1000 in Embodiment 1. The solid electrolyte composition 1000 includes an ion conductor 111 and a solvent 102. The ion conductor 111 includes a solid electrolyte 101, a binder 103, and a nitrogen-containing organic substance 104. The ion conductor 111 is dispersed or dissolved in the solvent 102. That is, the solid electrolyte 101, the binder 103, and the nitrogen-containing organic substance 104 are dispersed or dissolved in the solvent 102. The solid electrolyte 101 includes a sulfide solid electrolyte. The binder 103 includes a styrene-based elastomer. The nitrogen-containing organic substance 104 includes at least one selected from primary amines, secondary amines, aminohydroxy compounds, and diamines. The primary amines, secondary amines, aminohydroxy compounds, and diamines each have at least one selected from a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms. The ratio of the mass of the nitrogen-containing organic substance 104 to the mass of the solid electrolyte 101 is 0.30 mass % or more.

[0113] By the above technical configuration, a solid electrolyte composition 1000 with improved fluidity and dispersion stability can be obtained. By using the solid electrolyte composition 1000 with improved fluidity and dispersion stability, a large-area solid electrolyte sheet and a large-area battery can be efficiently manufactured. As a battery, for example, an all-solid secondary battery can be cited.

[0114] In the manufacture of the solid electrolyte composition 1000, an appropriate amount of nitrogen-containing organic matter 104 is added to the solid electrolyte 101. By adding a binder 103 thereto, a desired interaction is generated between the solid electrolyte 101, the binder 103 and the nitrogen-containing organic matter 104. As described above, the nitrogen-containing organic matter 104 includes at least one selected from primary amines, secondary amines, aminohydroxy compounds and diamines. By generating a desired interaction between these sites and the solid electrolyte 101, the dispersion stability and fluidity of the solid electrolyte composition 1000 can be improved. Primary amines, secondary amines, aminohydroxy compounds and diamines each have at least one selected from a chain alkyl having a carbon number of 8 or more and a chain alkenyl having a carbon number of 8 or more as a functional group. In addition, the binder 103 includes a styrene-based elastomer. Styrene-based elastomers have softness and elasticity. Therefore, it is believed that by generating a desired interaction between the above-mentioned functional groups in the nitrogen-containing organic matter 104 and the styrene-based elastomer, the dispersion stability and fluidity of the solid electrolyte composition 1000 can be improved. This can provide a solid electrolyte composition 1000 having improved fluidity and dispersion stability. Furthermore, by using the solid electrolyte composition 1000, a large-area solid electrolyte sheet and a large-area battery can be efficiently manufactured.

[0115] The dispersion stability of the solid electrolyte composition 1000 can be evaluated by the following method. First, 20 ml of the solid electrolyte composition 1000 is weighed in a 30 ml glass sample bottle. Then, the glass sample bottle is left to stand for a certain period of time, such as 1 day. Next, using a medicine spoon, the bottom of the glass sample bottle is visually confirmed to be a solid deposit (hard cake). Here, in the case where it is judged that there is no solid deposit, it is evaluated that the dispersion stability of the solid electrolyte composition 1000 is improved.

[0116] The fluidity of the solid electrolyte composition 1000 can be evaluated based on the shape of a flow curve obtained in a rate control mode using a viscosity / viscoelasticity measuring device. Figure 2 This is a graph for explaining a method for evaluating the fluidity of the solid electrolyte composition 1000 . Figure 2 In the figure, the vertical axis represents the viscosity of the solid electrolyte composition, and the horizontal axis represents the shear rate. The fluidity of the solid electrolyte composition 1000 can be evaluated by the following method. First, using a viscosity and viscoelasticity measuring device, the viscosity of the solid electrolyte composition at a shear rate of 0.1 / second to 1000 / second is measured at 25°C and in a speed control mode, and the measurement results are plotted in the above graph. In the graph, the viscosity of the solid electrolyte composition decreases continuously with increasing shear rate ( Figure 2 In the case of the curve A), it can be evaluated that the solid electrolyte composition has good fluidity. Figure 2 As shown in the curve B in FIG. 1 , in the case of a phenomenon in which the viscosity increases with an increase in the shear rate, i.e., so-called dilatancy, it can be evaluated that the fluidity of the solid electrolyte composition is poor. Figure 2 As shown in the curve C in FIG. 1 , when the viscosity changes discontinuously with respect to the increase in the shear rate, it can be evaluated that the fluidity of the solid electrolyte composition is poor. Figure 2 As shown by curve D in FIG. 1 , when the viscosity decreases sharply with an increase in the shear rate, it can be evaluated that the fluidity of the solid electrolyte composition is poor.

[0117] The solid electrolyte composition 1000 may be a slurry having fluidity. If the solid electrolyte composition 1000 has fluidity, a solid electrolyte sheet can be formed by a wet method such as a coating method.

[0118] The "solid electrolyte sheet" may be a self-supporting sheet member, or may be a solid electrolyte layer supported by an electrode or a substrate.

[0119] Hereinafter, the solid electrolyte composition 1000 will be described in detail.

[0120] [Solid electrolyte composition]

[0121] The solid electrolyte composition 1000 includes an ion conductor 111 and a solvent 102. The ion conductor 111 includes a solid electrolyte 101, a binder 103, and a nitrogen-containing organic substance 104. Hereinafter, the solid electrolyte 101, the binder 103, the nitrogen-containing organic substance 104, the ion conductor 111, and the solvent 102 will be described in detail.

[0122] <Solid electrolyte>

[0123] The solid electrolyte 101 includes a sulfide solid electrolyte. The sulfide solid electrolyte may contain lithium. By using a sulfide solid electrolyte containing lithium as the solid electrolyte 101, a lithium secondary battery can be manufactured using a solid electrolyte sheet obtained from the solid electrolyte composition 1000 including the sulfide solid electrolyte.

[0124] The solid electrolyte 101 may include a solid electrolyte other than a sulfide solid electrolyte such as an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, a complex hydride solid electrolyte, etc. Alternatively, the solid electrolyte 101 may be a sulfide solid electrolyte. In other words, the solid electrolyte 101 may include only a sulfide solid electrolyte.

[0125] In the present disclosure, the "oxide solid electrolyte" refers to a solid electrolyte containing oxygen. The oxide solid electrolyte may contain anions other than sulfur and halogen elements as anions other than oxygen.

[0126] In the present disclosure, "halide solid electrolyte" refers to a solid electrolyte containing a halogen element and not containing sulfur. In the present disclosure, a solid electrolyte containing no sulfur refers to a solid electrolyte represented by a composition formula containing no sulfur element. Therefore, a solid electrolyte containing a very small amount of sulfur, for example, a sulfur content of 0.1% by mass or less is included in the solid electrolyte containing no sulfur. In the halide solid electrolyte, oxygen may be contained as an anion other than the halogen element.

[0127] As sulfide solid electrolytes, for example, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 etc. LiX, Li2O, MO can be added to it q , Li p MO q The element X in "LiX" is at least one selected from F, Cl, Br and I. q ” and “Li p MOq The element M in "MO" is at least one selected from P, Si, Ge, B, Al, Ga, In, Fe and Zn. q ” and “Li p MO q " where p and q are each independently a natural number.

[0128] As a sulfide solid electrolyte, for example, Li2S-P2S5 glass ceramics can be used. LiX, Li2O, MO q , Li p MO q etc., and two or more selected from LiCl, LiBr and LiI may be added. Li2S-P2S5 glass ceramics are relatively soft materials, so a battery with higher durability can be manufactured by using a solid electrolyte sheet containing Li2S-P2S5 glass ceramics.

[0129] Examples of oxide solid electrolytes include NASICON solid electrolytes represented by LiTi2(PO4)3 and its element substitution products, (LaLi)TiO3-based perovskite solid electrolytes, and Li 14 ZnGe4O 16 , LISICON type solid electrolyte represented by Li4SiO4, LiGeO4 and their element substitution bodies, Li7La3Zr2O 12 Garnet-type solid electrolytes represented by its element substitution bodies, Li3PO4 and its N substitution bodies, glasses and glass ceramics based on Li-BO compounds such as LiBO2 and Li3BO3 and added with Li2SO4, Li2CO3, etc.

[0130] The halide solid electrolyte, for example, contains Li, M1 and X. M1 is at least one selected from metal elements and semi-metal elements other than Li. X is at least one selected from F, Cl, Br and I. The halide solid electrolyte has high thermal stability, so it is possible to improve the safety of the battery. In addition, the halide solid electrolyte does not contain sulfur, so it is possible to suppress the generation of hydrogen sulfide gas.

[0131] In the present disclosure, “metal elements” are B, Si, Ge, As, Sb, and Te.

[0132] In the present disclosure, “metal elements” are all elements contained in Groups 1 to 12 of the periodic table except hydrogen, and all elements contained in Groups 13 to 16 of the periodic table except B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se.

[0133] That is, in the present disclosure, "semi-metallic elements" and "metallic elements" are a group of elements that can become cations when forming an inorganic compound with a halogen element.

[0134] For example, the halide solid electrolyte may be a material represented by the following composition formula (1).

[0135] Li α M1 β X γ Formula (1)

[0136] In the above composition formula (1), α, β and γ are each independently a value greater than 0. γ may be 4, 6, or the like.

[0137] According to the above technical configuration, the ion conductivity of the halide solid electrolyte is improved, and therefore the ion conductivity of the solid electrolyte sheet formed from the solid electrolyte composition 1000 in Embodiment 1 is improved. When the solid electrolyte sheet is used in a battery, the cycle characteristics of the battery can be further improved.

[0138] In the above composition formula (1), the element M1 may include Y (=yttrium). That is, the halide solid electrolyte may include Y as a metal element.

[0139] The halide solid electrolyte containing Y can be represented by, for example, the following composition formula (2).

[0140] Li a Me b Y c X6···Formula (2)

[0141] In formula (2), a, b and c may satisfy a+mb+3c=6 and c>0. Element Me is at least one selected from metal elements and semi-metal elements other than Li and Y. m represents the valence of element Me. In addition, when element Me contains multiple elements, mb is the total value of the product of the composition ratio of each element and the valence of the element. For example, when Me contains element Me1 and element Me2, the composition ratio of element Me1 is b1, the valence of element Me1 is m1, the composition ratio of element Me2 is b2, and the valence of element Me2 is m2, mb is represented by m1b1+m2b2. In the above composition formula (2), element X is at least one selected from F, Cl, Br and I.

[0142] The element Me may be, for example, at least one selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, Gd, and Nb.

[0143] As the halide solid electrolyte, for example, the following materials can be used. According to the following materials, the ion conductivity of the solid electrolyte 101 is further improved, so the ion conductivity of the solid electrolyte sheet formed by the solid electrolyte composition 1000 can be improved. With this solid electrolyte sheet, the cycle characteristics of the battery can be further improved.

[0144] The halide solid electrolyte may be a material represented by the following composition formula (A1).

[0145] Li 6-3d Y d X6···Formula (A1)

[0146] In the composition formula (A1), the element X is at least one selected from Cl, Br and I. In the composition formula (A1), d satisfies 0<d<2.

[0147] The halide solid electrolyte may be a material represented by the following composition formula (A2).

[0148] Li3YX6···Formula (A2)

[0149] In composition formula (A2), element X is at least one selected from Cl, Br and I.

[0150] The halide solid electrolyte may be a material represented by the following composition formula (A3).

[0151] Li 3-3δ Y 1+δ Cl6···Formula (A3)

[0152] In composition formula (A3), δ satisfies 0<δ≤0.15.

[0153] The halide solid electrolyte may be a material represented by the following composition formula (A4).

[0154] Li 3-3δ Y 1+δ Br6···Formula (A4)

[0155] In composition formula (A4), δ satisfies 0<δ≤0.25.

[0156] The halide solid electrolyte may be a material represented by the following composition formula (A5).

[0157] Li 3-3δ+a Y 1+δ-a Me a Cl 6-x-y Br x I y ···Formula (A5)

[0158] In composition formula (A5), the element Me is at least one selected from Mg, Ca, Sr, Ba and Zn.

[0159] In addition, in the above composition formula (A5), -1<δ<2, 0<a<3, 0<(3-3δ+a), 0<(1+δ-a), 0≤x≤6, 0≤y≤6 and (x+y)≤6 are satisfied.

[0160] The halide solid electrolyte may be a material represented by the following composition formula (A6).

[0161] Li 3-3δ Y 1+δ-a Me a Cl 6-x-y Br x I y ···Formula (A6)

[0162] In composition formula (A6), the element Me is at least one selected from Al, Sc, Ga and Bi.

[0163] In addition, in the above composition formula (A6), -1<δ<1, 0<a<2, 0<(1+δ-a), 0≤x≤6, 0≤y≤6 and (x+y)≤6 are satisfied.

[0164] The halide solid electrolyte may be a material represented by the following composition formula (A7).

[0165] Li 3-3δ-a Y 1+δ-a Me a Cl 6-x-y Br x I y Formula (A7)

[0166] In the above composition formula (A7), the element Me is at least one selected from Zr, Hf and Ti.

[0167] In addition, in the above composition formula (A7), -1<δ<1, 0<a<1.5, 0<(3-3δ-a), 0<(1+δ-a), 0≤x≤6, 0≤y≤6 and (x+y)≤6 are satisfied.

[0168] The halide solid electrolyte may be a material represented by the following composition formula (A8).

[0169] Li 3-3δ-2a Y 1+δ-a Me a Cl 6-x-y Br x I y Formula (A8)

[0170] In composition formula (A8), the element Me is at least one selected from Ta and Nb.

[0171] In addition, in the above composition formula (A8), -1<δ<1, 0<a<1.2, 0<(3-3δ-2a), 0<(1+δ-a), 0≤x≤6, 0≤y≤6 and (x+y)≤6 are satisfied.

[0172] The halide solid electrolyte may be a compound containing Li, M2, O (oxygen) and X2. Element M2, for example, contains at least one selected from Nb and Ta. In addition, X2 is at least one selected from F, Cl, Br and I.

[0173] The compound containing Li, M2, X2 and O (oxygen) can be, for example, composed of the formula Li x M2O y X2 5+x-2y In other words, x can satisfy 0.1<x<7.0. y can satisfy 0.4<y<1.9.

[0174] As the halide solid electrolyte, more specifically, for example, Li3Y(Cl,Br,I)6, Li 2.7 Y 1.1 (Cl,Br,I)6, Li2Mg(F,Cl,Br,I)4, Li2Fe(F,Cl,Br,I)4, Li(Al,Ga,In)(F,Cl,Br,I)4, Li3(Al,Ga,In)(F,Cl,Br,I)6, Li3(Ca,Y,Gd)(Cl,Br,I)6, Li 2.7 (Ti,Al)F6、Li 2.5 (Ti, Al) F6, Li (Ta, Nb) O (F, Cl) 4, etc. In addition, in the present disclosure, when an element in a formula is expressed as "(Al, Ga, In)", the expression means at least one element selected from the element group in the brackets. That is, "(Al, Ga, In)" is synonymous with "at least one selected from Al, Ga and In". The same applies to other elements.

[0175] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound can have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt. Therefore, the ion conductivity can be further improved. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be used. One lithium salt can be used alone, or two or more can be used in combination.

[0176] As the complex hydride solid electrolyte, for example, LiBH4-Lii, LiBH4-P2S5, etc. can be used.

[0177] The shape of the solid electrolyte 101 is not particularly limited, and may be a needle shape, a sphere shape, an ellipsoidal sphere shape, etc. The solid electrolyte 101 may also be in the form of particles.

[0178] When the solid electrolyte 101 is in a particle shape (e.g., spherical shape), the median particle size of the solid electrolyte 101 may be 1 μm or more and 100 μm or more, or 1 μm or more and 10 μm or less. When the median particle size of the solid electrolyte 101 is 1 μm or more and 100 μm or less, the solid electrolyte 101 can be easily dispersed in the solvent 102.

[0179] When the solid electrolyte 101 is in the shape of particles (e.g., spheres), the median particle size of the solid electrolyte 101 may be 0.1 μm or more and 5 μm or more, or 0.5 μm or more and 3 μm or less. When the median particle size of the solid electrolyte 101 is 0.1 μm or more and 5 μm or less, the solid electrolyte sheet manufactured from the solid electrolyte composition 1000 can have a higher surface smoothness and a denser structure.

[0180] The median particle size is the particle size at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is obtained by a laser diffraction scattering method. The same applies to the following other materials.

[0181] The specific surface area of ​​the solid electrolyte 101 can be 0.1 m 2 / g or more and 100m 2 / g or less, or 1m 2 / g or more and 10m 2 / g or less. The specific surface area of ​​the solid electrolyte 101 is 0.1m 2 / g or more and 100m 2When the surface area is 1.377 square meters or less, the solid electrolyte 101 can be easily dispersed in the solvent 102. The specific surface area can be measured by the BET multipoint method using a gas adsorption measurement device.

[0182] The ionic conductivity of the solid electrolyte 101 can be 0.01 mS / cm 2 Above, it can be 0.1mS / cm 2 Above, can also be 1mS / cm 2 The ion conductivity of the solid electrolyte 101 is 0.01 mS / cm 2 In the above case, the output characteristics of the battery can be improved.

[0183] <Adhesive>

[0184] The binder 103 can improve the dispersion stability of the solid electrolyte 101 with respect to the solvent 102 in the solid electrolyte composition 1000. The binder 103 can improve the adhesion between particles of the solid electrolyte 101 in the solid electrolyte sheet.

[0185] The binder 103 includes a styrene-based elastomer. A styrene-based elastomer refers to an elastomer containing repeating units derived from styrene. A repeating unit refers to a molecular structure derived from a monomer, and is sometimes referred to as a constituent unit. Styrene-based elastomers are excellent in flexibility and elasticity, and are therefore suitable as a binder 103 for a solid electrolyte sheet. The content of repeating units derived from styrene in the styrene-based elastomer is not particularly limited, and is, for example, 10% by mass or more and 70% by mass or less.

[0186] Styrene-based elastomers can be block copolymers comprising a first block consisting of repeating units from styrene and a second block consisting of repeating units from a conjugated diene. As conjugated dienes, butadiene, isoprene, etc. can be cited. The repeating units from conjugated dienes can be hydrogenated (hydrogenated). That is, the repeating units from conjugated dienes may or may not have unsaturated bonds such as carbon-carbon double bonds. Block copolymers can have an arrangement of three blocks consisting of two first blocks and one second block. Block copolymers can be ABA-type triblock copolymers. In the triblock copolymer, A block is equivalent to the first block, and B block is equivalent to the second block. The first block functions, for example, as a hard segment. The second block functions, for example, as a soft segment.

[0187] As styrene elastomers, styrene-ethylene / butylene-styrene block copolymers (SEBS), styrene-ethylene / propylene-styrene block copolymers (SEPS), styrene-ethylene / ethylene / propylene-styrene block copolymers (SEEPS), styrene-butadiene rubber (SBR), styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), hydrogenated styrene-butadiene rubber (HSBR), etc. can be cited. SBR or SEBS can be included as a styrene elastomer in the adhesive 103. As an adhesive 103, a mixture containing two or more selected from these can be used. The softness and elasticity of the styrene elastomer are excellent, so by including the adhesive 103 of the styrene elastomer, the dispersion stability and fluidity of the solid electrolyte composition 1000 can be improved. In addition, the surface smoothness of the solid electrolyte sheet manufactured by the solid electrolyte composition 1000 can be improved. In addition, by including the adhesive 103 of the styrene elastomer, softness can be imparted to the solid electrolyte sheet. As a result, the electrolyte layer of a battery using the solid electrolyte sheet can be made thinner, and the energy density of the battery can be improved.

[0188] Styrene elastomer can be a styrene triblock copolymer. As styrene triblock copolymer, styrene-ethylene / butylene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), styrene-ethylene / ethylene / propylene-styrene block copolymer (SEEPS), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS) etc. can be cited. These styrene triblock copolymers are sometimes referred to as styrene thermoplastic elastomers. These styrene triblock copolymers have a tendency to be soft and high-strength.

[0189] The styrene elastomer may include styrene-butadiene rubber (SBR). The styrene elastomer may also be SBR. SBR has excellent softness and elasticity, and excellent filling property during heat compression, and is therefore particularly suitable as a binder for a solid electrolyte sheet.

[0190] Styrene elastomers may contain a modifying group. A modifying group refers to a functional group that chemically modifies all repeating units contained in a polymer chain, or a portion of repeating units contained in a polymer chain, or the terminal portion of a polymer chain. The modifying group may be introduced into a polymer chain by substitution reaction, addition reaction, etc. The modifying group may include, for example, elements such as O, N, S, F, Cl, Br, F, and Si, Sn, P, etc., which have relatively high electronegativity. By including a modifying group of such an element, polarity can be imparted to the polymer. As a modifying group, carboxylic acid group, anhydride group, acyl group, hydroxyl group, sulfonic group, sulfonyl group, phosphoric acid group, phosphonic acid group, isocyanate group, epoxy group, silyl group, amino group, nitrile group, nitro group, etc. may be cited. A specific example of anhydride group is maleic anhydride group. As a modifying group, it may be a functional group that can be introduced by reacting a modifier formed by the following compounds. As the compound of the modifier, epoxy compounds, ether compounds, ester compounds, isocyanate compounds, isothiocyanate compounds, isocyanuric acid derivatives, nitrogen-containing carbonyl compounds, nitrogen-containing vinyl compounds, nitrogen-containing epoxy compounds, mercapto derivatives, thiocarbonyl compounds, silicon halides, silicon epoxide compounds, vinyl silicon compounds, alkoxy silicon compounds, nitrogen-containing alkoxy silicon compounds, tin halides, organic tin carboxylate compounds, phosphite compounds, phosphine compounds, etc. can be cited. In the binder 103, when the styrene-based elastomer contains the above-mentioned modifying group, the dispersibility of the solid electrolyte 101 contained in the solid electrolyte composition 1000 can be further improved. In addition, through the interaction with the collector, the peel strength of the solid electrolyte sheet and the electrode sheet can be improved.

[0191] The styrene-based elastomer may contain a modified group having a nitrogen atom. The modified group having a nitrogen atom refers to a nitrogen-containing functional group, for example, an amino group such as an amine compound, etc. The position of the modified group may be the end of the polymer chain. The styrene-based elastomer having a modified group at the end of the polymer chain can have an effect similar to that of a so-called surfactant. That is, by using a styrene-based elastomer having a modified group at the end of the polymer chain, the modified group is adsorbed on the solid electrolyte 101, and the polymer chain can inhibit the aggregation between the particles of the solid electrolyte 101. As a result, the dispersibility of the solid electrolyte 101 can be further improved. The styrene-based elastomer may be, for example, a terminal amine-modified styrene-based elastomer. The styrene-based elastomer may be, for example, a styrene-based elastomer having a nitrogen atom at at least one end of the polymer chain and having a star-shaped polymer structure centered on a nitrogen-containing alkoxysilane substituent.

[0192] The styrene-based elastomer may include at least one selected from modified SBR and modified SEBS. Modified SBR refers to SBR into which a modifying group is introduced. Modified SEBS refers to SEBS into which a modifying group is introduced. Modified SBR and modified SEBS can make the solid electrolyte particles more dispersed, and are therefore particularly suitable as a binder for a solid electrolyte sheet.

[0193] The weight average molecular weight (M) of the styrene elastomer w ) can be 200,000 or more. The weight average molecular weight of the styrene elastomer can be 300,000 or more, 500,000 or more, 800,000 or more, or 1,000,000 or more. The upper limit of the weight average molecular weight is, for example, 1,500,000. By making the weight average molecular weight of the styrene elastomer above 200,000, the particles of the solid electrolyte 101 can be bonded with sufficient bonding strength. By making the weight average molecular weight of the styrene elastomer below 1,500,000, the ion conduction between the particles of the solid electrolyte 101 is not easily hindered by the binder 103, and the output characteristics of the battery can be improved. The weight average molecular weight of the styrene elastomer can be determined, for example, by gel permeation chromatography (GPC) using polystyrene as a standard sample. In other words, the weight average molecular weight is a value converted by polystyrene. In the GPC measurement, chloroform can be used as an eluent. When two or more peak tops are observed in a graph obtained by GPC measurement, the weight average molecular weight calculated from the entire peak range including the respective peak tops can be regarded as the weight average molecular weight of the styrene-based elastomer.

[0194] In styrene-based elastomers, the ratio of the degree of polymerization of repeating units derived from styrene to the degree of polymerization of repeating units derived from other than styrene is defined as m:n. In this case, the molar fraction (φ) of repeating units derived from styrene in styrene-based elastomers can be calculated by φ=m / (m+n). The molar fraction (φ) of repeating units derived from styrene in styrene-based elastomers can be calculated, for example, by proton nuclear magnetic resonance ( 1 It can be determined by HNMR) measurement.

[0195] In the styrene-based elastomer, the molar fraction (φ) of the repeating unit derived from styrene may be greater than 0.05 and less than 0.55, or may be greater than 0.1 and less than 0.3. By making the φ of the styrene-based elastomer greater than 0.05, the strength of the solid electrolyte sheet can be increased. By making the φ of the styrene-based elastomer less than 0.55, the softness of the solid electrolyte sheet can be improved.

[0196] The binder 103 may include a binder other than the styrene-based elastomer, such as a binder generally used as a binder for batteries. Alternatively, the binder 103 may be a styrene-based elastomer. In other words, the binder 103 may include only the styrene-based elastomer.

[0197] As adhesive, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate (PMMA), polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polycarbonate, polyether sulfone, polyether ketone, polyether ether ketone, polyphenylene sulfide, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose and ethyl cellulose etc. can be enumerated. As adhesive, the copolymer synthesized by two or more monomers selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, butadiene, isoprene, styrene, pentafluoropropylene, fluoromethyl vinyl ether, acrylate, acrylic acid and hexadiene can also be used. These can be used alone 1 kind, and two or more can be used in combination.

[0198] As adhesive, from the viewpoint of excellent adhesion, elastomer can be included. Elastomer refers to a polymer with rubber elasticity. The elastomer used as adhesive can be a thermoplastic elastomer or a thermosetting elastomer. As elastomer, in addition to the above-mentioned styrene-based elastomer, butadiene rubber (BR), isoprene rubber (IR), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR), hydrogenated isoprene rubber (HIR), hydrogenated butyl rubber (HIIR), hydrogenated nitrile rubber (HNBR), acrylate butadiene rubber (ABR) etc. can also be used. A mixture comprising two or more selected from these can also be used.

[0199] <Nitrogen-containing organic matter>

[0200] The nitrogen-containing organic substance 104 can improve the wettability and dispersibility of the solid electrolyte 101 with respect to the solvent 102 .

[0201] The nitrogen-containing organic substance 104 is an organic compound containing nitrogen atoms (N). The nitrogen-containing organic substance 104 includes at least one selected from primary amines, secondary amines, aminohydroxy compounds and diamines. The primary amines, secondary amines, aminohydroxy compounds and diamines each have at least one of a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms as a functional group. In addition, the ratio of the mass of the nitrogen-containing organic substance 104 to the mass of the solid electrolyte 101 is 0.30 mass % or more.

[0202] According to the above technical configuration, a solid electrolyte composition 1000 having improved fluidity and dispersion stability can be obtained. In addition, by using the solid electrolyte composition, a large-area solid electrolyte sheet and a large-area battery can be efficiently manufactured.

[0203] The chain alkyl group may be a straight chain alkyl group or a branched chain alkyl group. The straight chain alkyl group is a substituent composed of an aliphatic saturated hydrocarbon in which atoms other than hydrogen atoms, that is, carbon atoms, are linked together without branching.

[0204] The chain alkenyl group may be a straight-chain alkenyl group or a branched alkenyl group. A straight-chain alkenyl group is a substituent composed of an aliphatic unsaturated hydrocarbon in which atoms other than hydrogen atoms, i.e., carbon atoms, are connected without branches. There is no particular limitation on the position of the unsaturated bond in the alkenyl group. There is no particular limitation on the number of unsaturated bonds in the alkenyl group, which may be 1 or more than 2. The crystallinity of a compound having a straight-chain alkenyl group tends to be lower than that of a compound having a straight-chain alkyl group. Therefore, the fluidity of the solid electrolyte composition 1000 can be further improved by having a straight-chain alkenyl group in primary amines, secondary amines, aminohydroxy compounds, and diamines.

[0205] In the nitrogen-containing organic substance 104, the number of carbon atoms of the chain alkyl group or the chain alkenyl group may be 8 or more and 30 or less, 12 or more and 24 or less, or 16 or more and 22 or less. When the number of carbon atoms of the alkyl group or the alkenyl group is 8 or more, the dispersibility of the solid electrolyte 101 can be improved. When the number of carbon atoms of the alkyl group or the alkenyl group is 30 or less, the packing property of the ion conductor 111 can be improved.

[0206] The nitrogen-containing organic matter 104 may include organic matter derived from natural oils and fats. The nitrogen-containing organic matter 104 may also be an organic matter derived from natural oils and fats. In the nitrogen-containing organic matter 104, the alkyl group or alkenyl group may be a hydrocarbon group derived from natural oils and fats. Examples of the hydrocarbon group derived from natural oils and fats include coconut alkyl group, tallow alkyl group, hardened tallow alkyl group, oleyl group (a linear alkenyl group having 18 carbon atoms), and the like. Coconut alkyl groups include linear alkyl groups having 8 to 18 carbon atoms and linear alkenyl groups having 8 to 18 carbon atoms. Tallow alkyl groups include linear alkyl groups having 14 to 18 carbon atoms and linear alkenyl groups having 8 to 18 carbon atoms. Hardened tallow alkyl groups include linear alkyl groups having 14 to 18 carbon atoms.

[0207] The nitrogen-containing organic substance 104 may contain at least one selected from primary amines and secondary amines. The nitrogen-containing organic substance 104 may be a primary amine or a secondary amine. A primary amine refers to a compound in which one hydrogen atom of ammonia is replaced by a hydrocarbon group. The hydrocarbon group is a chain alkyl group having 8 or more carbon atoms or a chain alkenyl group having 8 or more carbon atoms. The primary amine may not contain a hydroxyl group. A secondary amine refers to a compound in which two hydrogen atoms of ammonia are replaced by hydrocarbon groups. The types of the two hydrocarbon groups contained in the secondary amine may be the same or different. The hydrocarbon group contains at least one selected from a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms. The secondary amine may not contain a hydroxyl group.

[0208] Examples of the primary amine include octylamine, dodecylamine, laurylamine, myristicamine, hexadecylamine, stearylamine, oleylamine, coconut alkylamine, tallow alkylamine, hardened tallow alkylamine, soybean alkylamine, and coconut amine.

[0209] Examples of the secondary amine include N-methyloctadecylamine, di-hardened tallow alkylamine, dicoconut alkylamine, and dioleylamine.

[0210] The nitrogen-containing organic substance 104 may include an aminohydroxy compound. The nitrogen-containing organic substance 104 may also be an aminohydroxy compound. An aminohydroxy compound refers to a compound having at least one nitrogen atom and at least one hydroxyl group in a molecule. In addition, the aminohydroxy compound has at least one selected from a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms.

[0211] The aminohydroxy compound may include a structure represented by the following formula (3).

[0212]

[0213] In formula (3), -R-OH is -(CH2) n -OH or -(CH2CH2O) m -H. -(CH2) n The number of carbon atoms of n, i.e., the alkylene group in -OH may be 2 to 6, 2 to 4, or 2. m may be 1 to 5, or 1 to 2. In formula (3), the wavy line indicates a bonding point.

[0214] When an aminohydroxy compound is used as the nitrogen-containing organic substance 104 , the dispersibility of the solid electrolyte 101 can be further improved.

[0215] The aminohydroxy compound may be an alkanolamine. An alkanolamine is a compound having an amino group (-NH2) and a hydroxyl group (-OH) in the molecule. An alkanolamine may be a compound in which the hydrogen atoms of an alkane are replaced by an amino group and a hydroxyl group, or a compound in which the hydrogen atoms of an alkene are replaced by an amino group and a hydroxyl group. Even when an alkanolamine is used as the nitrogen-containing organic substance 104, the dispersibility of the solid electrolyte 101 can be further improved.

[0216] Examples of the aminohydroxy compound include polyoxyethylene alkylamines, polyoxyethylene alkenylamines, N,N-bis(2-hydroxyethyl)alkylamines, N,N-bis(2-hydroxyethyl)alkenylamines, N,N',N'-tris(2-hydroxyethyl)-N-alkyl-1,3-diaminopropanes, N,N',N'-tris(2-hydroxyethyl)-N-alkenyl-1,3-diaminopropanes, triethanolamine monofatty acid esters, triethanolamine difatty acid esters, N,N-bis(2-hydroxyethyl)oleylamine, and 1-hydroxyethyl-2-alkenyl imidazoline.

[0217] The nitrogen-containing organic substance 104 may be a commercially available product. As the nitrogen-containing organic substance 104, for example, a commercially available reagent, dispersant, wetting agent, or surfactant may be used.

[0218] The nitrogen-containing organic matter 104 can use polyoxyethylene alkylamine or polyoxyethylene alkenylamine as the aminohydroxy compound. The alkyl group contained in the polyoxyethylene alkylamine and the alkenyl group contained in the polyoxyethylene alkenylamine can be the above-mentioned alkyl group derived from natural oils and alkenyl groups derived from natural oils and fats. The average number of added moles of ethylene oxide contained in the polyoxyethylene alkylamine or polyoxyethylene alkenylamine can be 1 or 2. The alkyl group of the polyoxyethylene alkylamine can be 8 or more and 22 or less carbon atoms. The alkenyl group of the polyoxyethylene alkenylamine can be 8 or more and 22 or less carbon atoms. As polyoxyethylene alkylamine or polyoxyethylene alkenylamine, for example, Amiet manufactured by Kao Corporation, Liponol manufactured by Lion Specialty Chemicals, and Nymeen manufactured by NOF Corporation can be cited. "Amiet" is a registered trademark of Kao Corporation. "Lipono" is a registered trademark of Lion Specialty Chemicals. "Nymeen" is a registered trademark of NOF Corporation.

[0219] The nitrogen-containing organic matter 104 can use triethanolamine difatty acid ester as the aminohydroxy compound. Triethanolamine difatty acid ester is a compound formed by ester condensation of triethanolamine and two fatty acids. There is no particular limitation on the type of fatty acid contained in the triethanolamine difatty acid ester, and fatty acids having a hydrocarbon group with 16 to 18 carbon atoms can be used. Examples of fatty acids include palmitic acid, oleic acid, linoleic acid, linolenic acid, and the like. Examples of triethanolamine difatty acid ester include DISPERBYK-108 manufactured by BYK. "DISPERBYK" is a registered trademark of BYK.

[0220] The nitrogen-containing organic substance 104 may use N,N-bis(2-hydroxyethyl)alkenylamine as the aminohydroxy compound. The number of carbon atoms in the alkenyl group may be 10 to 22, or 14 to 20. The number of unsaturated bonds in the alkenyl group is not particularly limited, and may be 1 or 2.

[0221] The nitrogen-containing organic substance 104 can use 1-hydroxyethyl-2-alkenyl imidazoline as an aminohydroxy compound. The alkenyl group contained in the 1-hydroxyethyl-2-alkenyl imidazoline can be a hydrocarbon group having a carbon number of 13 or more and 17 or less. The number of unsaturated bonds contained in the alkenyl group can be 1 or more and 3 or less. As 1-hydroxyethyl-2-alkenyl imidazoline, DISPERBYK-109 manufactured by BYK and Homogenol L-95 manufactured by Kao Corporation can be cited. "Homogenol" is a registered trademark of Kao Corporation.

[0222] The nitrogen-containing organic substance 104 may include a diamine. The nitrogen-containing organic substance 104 may also be a diamine. A diamine is a compound having two amino groups in one molecule. In addition, the diamine has at least one selected from a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms.

[0223] The diamine may include a structure represented by the following formula (4).

[0224]

[0225] In formula (4), R represents an alkylene group. The number of carbon atoms in the alkylene group may be 2 or more and 6 or less, 2 or more and 4 or less, or 3. In formula (4), the wavy line represents a bonding point.

[0226] Among the nitrogen-containing organic substances 104, examples of diamines include N-coconut alkyl-1,3-diaminopropane, N-tallow alkyl-1,3-diaminopropane, N-hardened tallow alkyl-1,3-diaminopropane, oleyl propylene diamine, and behenyl propylene diamine. The tallow alkyl group includes a linear alkyl group having 14 to 18 carbon atoms and a linear alkenyl group having 8 to 18 carbon atoms.

[0227] The nitrogen-containing organic substance 104 may include oleylamine. The nitrogen-containing organic substance 104 may also be oleylamine. Oleylamine is liquid at room temperature. In addition, oleylamine is a primary amine having a long-chain alkenyl group. Oleylamine can further improve the dispersibility of the solid electrolyte 101. In addition, by using oleylamine, the filling property of the press-molded ion conductor 111 can be further improved.

[0228] The iodine value of the nitrogen-containing organic substance 104 may be 15 or more, 50 or more, 90 or more, or 100 or more. When the iodine value of the nitrogen-containing organic substance 104 is 15 or more, the fluidity of the solid electrolyte composition 1000 can be further improved. The iodine value of the nitrogen-containing organic substance 104 may be 150 or less. When the iodine value of the nitrogen-containing organic substance 104 is 150 or less, reactions such as oxidative decomposition can be suppressed. As a result, the durability of the battery made using the solid electrolyte composition 1000 can be improved. The iodine value is the value of the mass of iodine contained in 100g of the sample. The unit of the iodine value is expressed as 12g / 100g. The iodine value of the nitrogen-containing organic substance 104 can be obtained by the Weiss method. However, when the iodine value obtained by the Weiss method is 3 or less, the iodine value of the nitrogen-containing organic substance 104 uses the value obtained by NMR measurement. In the NMR measurement, for example, decamethylcyclopentasiloxane can be used as an internal standard substance to obtain the iodine value of the nitrogen-containing organic substance 104.

[0229] <Ion conductor>

[0230] As described above, the ion conductor 111 includes the solid electrolyte 101, the binder 103, and the nitrogen-containing organic substance 104. In the ion conductor 111, a plurality of particles of the solid electrolyte 101 are bound together via the binder 103. In the ion conductor 111, the particles of the solid electrolyte 101 are dispersed by the nitrogen-containing organic substance 104 adsorbed on the solid electrolyte 101.

[0231] In the ion conductor 111, the ratio of the mass of the binder 103 to the mass of the solid electrolyte 101 is not particularly limited, and may be 0.1% by mass or more and 10% by mass or less, 0.5% by mass or more and 5% by mass or less, or 1% by mass or more and 3% by mass or less. When the ratio of the mass of the binder 103 to the mass of the solid electrolyte 101 is 0.1% by mass or more, the strength of the solid electrolyte sheet manufactured from the solid electrolyte composition 1000 can be improved. When the ratio of the mass of the binder 103 to the mass of the solid electrolyte 101 is 10% by mass or less, the reduction in the ion conductivity of the ion conductor 111 can be suppressed.

[0232] As described above, in the ion conductor 111, the ratio of the mass of the nitrogen-containing organic matter 104 to the mass of the solid electrolyte 101 is 0.30 mass % or more. By making the ratio of the mass of the nitrogen-containing organic matter 104 to the mass of the solid electrolyte 101 to be 0.30 mass % or more, a solid electrolyte composition with improved fluidity and dispersion stability can be obtained. By using a solid electrolyte composition with improved fluidity and dispersion stability, a large-area solid electrolyte sheet and a large-area battery can be efficiently manufactured. The ratio of the mass of the nitrogen-containing organic matter 104 to the mass of the solid electrolyte 101 can be 0.60 mass % or more, or 1.0 mass % or more. By making the ratio of the mass of the nitrogen-containing organic matter 104 to the mass of the solid electrolyte 101 to be 0.60 mass % or more, a solid electrolyte composition with further improved fluidity and dispersion stability can be obtained. The ratio of the mass of the nitrogen-containing organic matter 104 to the mass of the solid electrolyte 101 can be 10 mass % or less, 5 mass % or less, or 1 mass % or less. When the ratio of the mass of nitrogen-containing organic matter 104 to the mass of solid electrolyte 101 is 10 mass % or less, a decrease in the ion conductivity of ion conductor 111 and a decrease in the strength of the solid electrolyte sheet can be suppressed.

[0233] The ion conductor 111 can be produced, for example, by mixing the solid electrolyte 101, the binder 103, and the nitrogen-containing organic substance 104. There is no particular limitation on the mixing method, and for example, a method of mechanically crushing and mixing the solid electrolyte 101, the binder 103, and the nitrogen-containing organic substance 104 in a dry manner can be cited. The following wet method can also be used: prepare a solution or dispersion containing the binder 103 and a solution or dispersion containing the nitrogen-containing organic substance 104, disperse the solid electrolyte 101 in these solutions or dispersions, and mix them. By the wet method, the binder 103, the nitrogen-containing organic substance 104, and the solid electrolyte 101 can be easily and uniformly mixed. The ion conductor 111 can be produced in a solvent by a wet method, thereby producing the solid electrolyte composition 1000.

[0234] <Solvent>

[0235] The solvent 102 may be an organic solvent. An organic solvent refers to a carbon-containing compound, such as a compound containing elements such as carbon, hydrogen, nitrogen, oxygen, sulfur, and halogen.

[0236] The solvent 102 may include at least one selected from hydrocarbons, compounds having a halogen group, and compounds having an ether bond.

[0237] Hydrocarbons are compounds consisting only of carbon and hydrogen. Hydrocarbons may be aliphatic hydrocarbons. Hydrocarbons may be saturated hydrocarbons or unsaturated hydrocarbons. Hydrocarbons may be linear or branched. There is no particular limitation on the number of carbons contained in hydrocarbons, and it may be 7 or more. By using hydrocarbons, a solid electrolyte composition 1000 having improved dispersibility of the ion conductor 111 can be obtained. In addition, a decrease in the ion conductivity of the solid electrolyte 101 due to mixing with the solvent 102 can be suppressed.

[0238] The hydrocarbon may have a ring structure. The ring structure may be an alicyclic hydrocarbon or an aromatic hydrocarbon. The ring structure may be a monocyclic or a polycyclic. Since the hydrocarbon has a ring structure, the ion conductor 111 can be easily dispersed in the solvent 102. From the viewpoint of improving the dispersibility of the ion conductor 111 in the solid electrolyte composition 1000, the hydrocarbon may contain an aromatic hydrocarbon. That is, the solvent 102 may contain an aromatic hydrocarbon. The hydrocarbon may be an aromatic hydrocarbon. Styrene-based elastomers are easily dissolved in aromatic hydrocarbons. Therefore, in the case where the binder 103 contains a styrene-based elastomer and the solvent 102 contains an aromatic hydrocarbon, in the solid electrolyte composition 1000, the binder 103 can be more effectively adsorbed on the solid electrolyte 101. Thus, the performance of the solid electrolyte composition 1000 in retaining the solvent can be further improved.

[0239] In the compound having a halogen group, the part other than the halogen group may be composed only of carbon and hydrogen. That is, the compound having a halogen group refers to a compound in which at least one hydrogen atom contained in a hydrocarbon is replaced by a halogen group. As the halogen group, F, Cl, Br and I can be cited. As the halogen group, at least one selected from F, Cl, Br and I can be used. The compound having a halogen group has polarity. By using a compound having a halogen group in the solvent 102, the ion conductor 111 can be easily dispersed in the solvent 102, so that a solid electrolyte composition 1000 with improved dispersibility can be obtained. As a result, the reduction in ion conductivity when a solid electrolyte sheet is made using the solid electrolyte composition 1000 can be suppressed. In addition, the solid electrolyte sheet can have a denser structure.

[0240] There is no particular limitation on the number of carbon atoms contained in the compound having a halogen group, and the number of carbon atoms may be 7 or more. Thus, the compound having a halogen group is not easily volatile, and thus a solid electrolyte composition having improved fluidity can be obtained. In addition, by using a compound having a halogen group, the solid electrolyte composition 1000 can be stably manufactured. The compound having a halogen group can have a large molecular weight. That is, the compound having a halogen group can have a high boiling point.

[0241] The compound having a halogen group may have a ring structure. The ring structure may be an alicyclic hydrocarbon or an aromatic hydrocarbon. The ring structure may be a monocyclic or a polycyclic. The compound having a halogen group may have a ring structure, so that the ion conductor 111 can be easily dispersed in the solvent 102. From the viewpoint of improving the dispersibility of the ion conductor 111 in the solid electrolyte composition 1000, the compound having a halogen group may include an aromatic hydrocarbon. The compound having a halogen group may be an aromatic hydrocarbon.

[0242] The compound having a halogen group may have only a halogen group as a functional group. In this case, there is no particular limitation on the number of halogens contained in the compound having a halogen group. As the halogen group, at least one selected from F, Cl, Br and I can be used. By using such a compound in the solvent 102, the ion conductor 111 can be easily dispersed in the solvent 102, so that a solid electrolyte composition 1000 with improved dispersibility can be obtained. As a result, the reduction in ion conductivity when a solid electrolyte sheet is made from the solid electrolyte composition 1000 can be suppressed. In addition, the solid electrolyte sheet made from the solid electrolyte composition 1000 tends to have a dense structure with few pinholes, bumps, etc.

[0243] The compound having a halogen group may be a halogenated hydrocarbon. A halogenated hydrocarbon is a compound in which all hydrogen contained in a hydrocarbon is replaced by a halogen group. By using a halogenated hydrocarbon in the solvent 102, the ion conductor 111 can be easily dispersed in the solvent 102, so that a solid electrolyte composition 1000 with improved dispersibility can be obtained. As a result, the decrease in ion conductivity when a solid electrolyte sheet is made from the solid electrolyte composition 1000 can be suppressed. In addition, a solid electrolyte sheet made from the solid electrolyte composition 1000 can easily have a dense structure with few pinholes, bumps, etc.

[0244] In the compound having an ether bond, the portion other than the ether bond may be composed only of carbon and hydrogen. That is, the compound having an ether bond refers to a compound in which at least one CC bond contained in a hydrocarbon is replaced by a COC bond. The compound having an ether bond may have polarity. By using a compound having an ether bond in the solvent 102, the ion conductor 111 can be easily dispersed in the solvent 102. Therefore, a solid electrolyte composition 1000 with improved dispersibility can be obtained. As a result, the decrease in ion conductivity when a solid electrolyte sheet is made from the solid electrolyte composition 1000 can be suppressed. In addition, the solid electrolyte sheet made from the solid electrolyte composition 1000 can have a denser structure.

[0245] The compound having an ether bond may have a ring structure. The ring structure may be an alicyclic hydrocarbon or an aromatic hydrocarbon. The ring structure may be a monocyclic or a polycyclic. Since the compound having an ether bond has a ring structure, the ion conductor 111 can be easily dispersed in the solvent 102. From the viewpoint of improving the dispersibility of the ion conductor 111 in the solid electrolyte composition 1000, the compound having an ether bond may include an aromatic hydrocarbon. The compound having an ether bond may be an aromatic hydrocarbon substituted with an ether group.

[0246] Examples of the solvent 102 include ethylbenzene, mesitylene, pseudocumene, p-xylene, cumene, tetralin, m-xylene, dibutyl ether, 1,2,4-trichlorobenzene, chlorobenzene, 2,4-dichlorotoluene, anisole, o-chlorotoluene, m-dichlorobenzene, p-chlorotoluene, o-dichlorobenzene, 1,4-dichlorobutane, and 3,4-dichlorotoluene. These may be used alone or in combination of two or more.

[0247] From the viewpoint of cost, commercially available xylene, that is, mixed xylene, can be used as the solvent 102. For example, a mixed xylene in which o-xylene, m-xylene, p-xylene and ethylbenzene are mixed in a mass ratio of 24:42:18:16 can be used as the solvent 102.

[0248] The solvent 102 may also contain tetralin. Tetralin has a relatively high boiling point. The fluidity and dispersion stability of the solid electrolyte composition are improved by tetralin. In addition, tetralin can not only improve the solvent retention performance of the solid electrolyte composition 1000, but also stably manufacture the solid electrolyte composition 1000 by a kneading process.

[0249] The boiling point of the solvent 102 may be 100° C. or more and 250° C. or less, 130° C. or more and 230° C. or less, 150° C. or more and 220° C. or less, or 180° C. or more and 210° C. or less. The solvent 102 may be a liquid at room temperature (25° C.). Such a solvent is not easily volatile at room temperature, so the solid electrolyte composition 1000 can be stably manufactured. Therefore, a solid electrolyte composition 1000 that can be easily applied to the surface of an electrode or a substrate can be obtained. The solvent 102 contained in the solid electrolyte composition 1000 can be easily removed by drying described later.

[0250] The moisture content of the solvent 102 may be less than 10 mass ppm. By reducing the moisture content, the decrease in ionic conductivity caused by the reaction of the solid electrolyte 101 can be suppressed. As a method for reducing the moisture content, a dehydration method using a molecular sieve, a dehydration method using an inert gas such as nitrogen or argon for bubbling, etc. can be cited. By using an inert gas for bubbling, deoxygenation can be performed while reducing the moisture content. The moisture content can be measured using a Karl-Fischer moisture measuring device.

[0251] The solvent 102 disperses the ion conductor 111. The solvent 102 may be a liquid capable of dispersing the solid electrolyte 101. The solid electrolyte 101 may not be dissolved in the solvent 102. Since the solid electrolyte 101 is not dissolved in the solvent 102, it is easy to maintain the ion conductive phase when the solid electrolyte 101 is manufactured. Therefore, the solid electrolyte sheet manufactured by using the solid electrolyte composition 1000 can suppress the decrease in ion conductivity.

[0252] The solvent 102 can partially or completely dissolve the solid electrolyte 101. By dissolving the solid electrolyte 101 in the solvent 102, the density of the solid electrolyte sheet manufactured using the solid electrolyte composition 1000 can be improved.

[0253] <Solid electrolyte composition>

[0254] The solid electrolyte composition 1000 may be in a paste state or in a state of a dispersion liquid. The ion conductor 111 is, for example, a particle. In the solid electrolyte composition 1000, the particles of the ion conductor 111 are mixed with the solvent 102. In the manufacture of the solid electrolyte composition 1000, there is no particular limitation on the mixing method of the ion conductor 111 and the solvent 102, that is, the mixing method of the solid electrolyte 101, the solvent 102, the binder 103 and the nitrogen-containing organic matter 104. For example, a mixing method using a mixing device such as a stirring type, a vibration type, an ultrasonic type, and a rotating type can be cited. For example, a mixing method using a high-speed homogenizer, a thin film rotating high-speed mixer, an ultrasonic homogenizer, a high-pressure homogenizer, a ball mill, a bead mill, a planetary mixer, a sand mill, a roller mill, a kneader and other dispersing and kneading devices can be cited. These mixing methods can be used alone or in combination of two or more.

[0255] As a method for mixing the solid electrolyte 101, the solvent 102, the binder 103, and the nitrogen-containing organic matter 104, a high shear treatment using a high-speed homogenizer or a high shear treatment using an ultrasonic homogenizer can be adopted. Through these high shear treatments, the nitrogen-containing organic matter 104 can be effectively adsorbed on the particle surface of the solid electrolyte 101. As a result, the dispersion stability of the solid electrolyte composition 1000 produced by these high shear treatments can be further improved.

[0256] [Method for producing solid electrolyte composition]

[0257] The solid electrolyte composition 1000 is manufactured, for example, by the following method. First, the solid electrolyte 101 and the solvent 102 are mixed, and then a solution containing a binder 103 and a solution containing a nitrogen-containing organic matter 104 are added. The obtained mixed solution is subjected to high-speed shear treatment using an in-line disperser and pulverizer. Through such a process, an ion conductor 111 is formed, and the ion conductor 111 is dispersed and stabilized in the solvent 102, so that a solid electrolyte composition 1000 with improved fluidity can be manufactured. In addition, from the perspective of manufacturing a solid electrolyte composition 1000 with improved fluidity, the high-speed shear treatment can be carried out under the condition of a circumferential speed that does not produce crushing of the solid electrolyte 101 particles and produces fragmentation between the solid electrolyte 101 particles. The solid electrolyte composition 1000 can also be manufactured by mixing the solvent 102 and the pre-made ion conductor 111 and subjecting the obtained mixed solution to high-speed shear treatment.

[0258] The solid electrolyte composition 1000 can be manufactured by the following method. First, the solid electrolyte 101 and the solvent 102 are mixed, and then a solution containing a binder 103 and a solution containing a nitrogen-containing organic matter 104 are added. The resulting mixed solution is subjected to high shear treatment using an ultrasonic homogenizer. Through such a process, an ion conductor 111 is formed, and the ion conductor 111 is dispersed and stabilized in the solvent 102, so that a solid electrolyte composition 1000 with further improved fluidity can be manufactured. The solid electrolyte composition 1000 can also be manufactured by mixing a solvent 102 and a pre-made ion conductor 111, and subjecting the resulting mixed solution to high shear treatment using ultrasound.

[0259] From the viewpoint of producing a solid electrolyte composition 1000 with further improved fluidity, high-speed shear treatment or high-speed shear treatment using ultrasonic waves can be performed under conditions that do not cause pulverization of solid electrolyte 101 particles but cause fragmentation between solid electrolyte 101 particles.

[0260] The solution containing the binder 103 is, for example, a solution containing the binder 103 and the solvent 102. The composition of the solvent contained in the solution containing the binder 103 may be the same as or different from the composition of the solvent contained in the dispersion of the solid electrolyte 101.

[0261] The solution containing nitrogen-containing organic substance 104 is, for example, a solution containing nitrogen-containing organic substance 104 and solvent 102. The composition of the solvent contained in the solution containing nitrogen-containing organic substance 104 may be the same as or different from the composition of the solvent contained in the dispersion of solid electrolyte 101.

[0262] The solid content concentration of the solid electrolyte composition 1000 is appropriately determined according to the particle size of the solid electrolyte 101, the specific surface area of ​​the solid electrolyte 101, the type of the solvent 102, the type of the binder 103, and the type of the nitrogen-containing organic matter 104. The solid content concentration can be 20% by mass or more and 70% by mass or less, or 30% by mass or more and 60% by mass or less. By making the solid content concentration 20% by mass or more, the solid electrolyte composition 1000 has a desired viscosity, so it is easy to apply the solid electrolyte composition 1000 to a substrate such as an electrode. By making the solid content concentration 70% by mass or less, the wet film thickness when the solid electrolyte composition 1000 is applied to the substrate can be relatively thickened. Thus, a solid electrolyte sheet with a more uniform film thickness can be manufactured.

[0263] The fluidity of the solid electrolyte composition 1000 can be evaluated based on the value of the viscosity ratio obtained using a viscosity / viscoelasticity measuring device. Alternatively, the fluidity of the solid electrolyte composition 1000 can be evaluated by evaluating rheological properties using a viscosity / viscoelasticity measuring device.

[0264] The fluidity of the solid electrolyte composition 1000 can be evaluated, for example, by the following method. The viscosity of the solid electrolyte composition 1000 measured at 25°C and a shear rate of 1 / sec using a viscosity / viscoelasticity measuring device in a speed control mode is defined as viscosity η1. The viscosity of the solid electrolyte composition 1000 measured at 25°C and a shear rate of 100 / sec using a viscosity / viscoelasticity measuring device in a speed control mode is defined as viscosity η2. The fluidity of the solid electrolyte composition 1000 can be evaluated by the ratio η1 / η2 of the viscosity η1 to the viscosity η2.

[0265] In the solid electrolyte composition 1000, η1 / η2 may be 1.4 or more, 3.0 or more, 5.0 or more, 10 or more, or 20 or more. By making η1 / η2 1.4 or more, the dispersion stability of the solid electrolyte composition 1000 can be further improved. In addition, sagging when applying the solid electrolyte composition 1000 can be suppressed. The upper limit value of η1 / η2 is, for example, 30. By making η1 / η2 30 or less, the uniformity of the film thickness of the solid electrolyte sheet 301 manufactured from the solid electrolyte composition 1000 can be improved.

[0266] The fluidity of the solid electrolyte composition 1000 can be evaluated by evaluating the rheological properties. For example, the Casson yield value, the value of the storage elastic modulus G', and the value of the loss tangent tan δ are used in the evaluation of the rheological properties.

[0267] In the solid electrolyte composition 1000, the rheological properties can be evaluated based on the Casson yield value obtained using a viscosity·viscoelasticity measuring device in a speed control mode. The Casson yield value can be calculated by the following method. First, the shear stress (S) of the solid electrolyte composition 1000 at a shear rate (D) from 0.1 / second to 1000 / second is measured using a viscosity·viscoelasticity measuring device at 25°C and in a speed control mode. Using the obtained numerical values ​​of the shear rate and the shear stress, the slope a and the intercept b are determined based on the following relationship. The Casson yield value is the value of the square of the intercept b in the relationship shown below.

[0268]

[0269] In the solid electrolyte composition 1000, the Casson yield value may be greater than 0.05 Pa and less than 4.5 Pa, or greater than 0.1 Pa and less than 2.0 Pa. By setting the Casson yield value to be greater than 0.05 Pa, it is easy to apply the solid electrolyte composition 1000 to a substrate. By setting the Casson yield value to be less than 4.5 Pa, a coating film having a more uniform thickness can be manufactured.

[0270] In the solid electrolyte composition 1000 , rheological properties can be evaluated based on the storage elastic modulus G′ and the loss tangent tan δ obtained in a strain control mode using a viscosity / viscoelasticity measuring device.

[0271] The storage elastic modulus G' and the loss tangent tanδ can be measured by the following method. First, using a viscosity and viscoelasticity measuring device, shear is applied to the solid electrolyte composition with a strain (γ) from 0.01% to 10000% under the conditions of 25°C, a frequency of 1Hz and a strain control mode. Then, the storage elastic modulus G' and the loss tangent tanδ are measured when γ is recovered from 10000% to 0.01%. At this time, the storage elastic modulus G' and the loss tangent tanδ under γ = 130%, i.e., high strain conditions are obtained. In addition, the storage elastic modulus G' and the loss tangent tanδ under γ = 0.1%, i.e., low strain conditions are obtained.

[0272] In the solid electrolyte composition 1000, the storage elastic modulus G' at γ = 130% can be greater than 0.10Pa and less than 2.0Pa, or greater than 0.2Pa and less than 1.0Pa. In addition, the loss tangent tanδ at γ = 130% can be greater than 2.5 and less than 30, or greater than 4.0 and less than 15. By adjusting at least one of the storage elastic modulus G' and the loss tangent tanδ within the above range, the solid electrolyte composition 1000 can have good fluidity. Therefore, the solid electrolyte composition 1000 can be easily transported using an apparatus or the like.

[0273] In the solid electrolyte composition 1000, the storage elastic modulus G' when γ = 0.1% can be 1.0Pa or more and 80Pa or less, or 10Pa or more and 70Pa or less. In addition, the loss tangent tanδ when γ = 0.1% can be 0.4 or more and 3.9 or less, or 0.5 or more and 3.0 or less, or 0.6 or more and 2.0 or less. By adjusting the storage elastic modulus G' when γ = 0.1% to 1.0Pa or more, or adjusting the loss tangent tanδ to 3.9 or less, the solid electrolyte composition 1000 can be easily applied to a substrate or the like. Thus, in the coating obtained using the solid electrolyte composition 1000, the uniformity of the film thickness can be improved. By adjusting the storage elastic modulus G' when γ = 0.1% to 80Pa or less, or adjusting the loss tangent tanδ to 0.4 or more, for example, when the solid electrolyte composition 1000 is applied to a substrate or the like, the solid electrolyte composition 1000 is easily wetted and spread. As a result, in the coating film obtained using the solid electrolyte composition 1000 , the uniformity of the film thickness can be further improved.

[0274] (Implementation Method 2)

[0275] Embodiment 2 will be described below, and descriptions overlapping with those of Embodiment 1 will be appropriately omitted.

[0276] The electrode composition 2000 may be a slurry having fluidity. If the electrode composition 2000 has fluidity, an electrode sheet may be formed by a wet method such as a coating method. The "electrode sheet" may be a self-supporting sheet component, or a positive electrode layer or a negative electrode layer supported by a current collector, a substrate, or an electrode assembly.

[0277] [Electrode composition]

[0278] Figure 3Schematic diagram of electrode composition 2000 in Embodiment 2. Electrode composition 2000 includes ion conductor 121 and solvent 102. Ion conductor 121 includes solid electrolyte 101, binder 103, nitrogen-containing organic matter 104, and active material 201. Ion conductor 121 is dispersed or dissolved in solvent 102. That is, solid electrolyte 101, binder 103, nitrogen-containing organic matter 104, and active material 201 are dispersed or dissolved in solvent 102. In other words, electrode composition 2000 includes active material 201 and solid electrolyte composition 1000. Solid electrolyte composition 1000 includes solid electrolyte 101, solvent 102, binder 103, and nitrogen-containing organic matter 104. Solid electrolyte composition 1000 is as described in Embodiment 1 above. Electrode composition 2000 is obtained by adding active material 201 to solid electrolyte composition 1000. The characteristics and effects of electrode composition 2000 are the same as those of solid electrolyte composition 1000. Hereinafter, the active material 201 will be described in detail.

[0279] <Active substances>

[0280] The active material 201 in Embodiment 2 includes a material having the property of absorbing and releasing metal ions (e.g., lithium ions). The active material 201 includes, for example, a positive electrode active material or a negative electrode active material. When the electrode composition 2000 includes the active material 201, an electrode sheet obtained from the electrode composition 2000 can be used to manufacture a lithium secondary battery.

[0281] The active material 201 includes a positive electrode active material. For example, as a positive electrode active material, a material having the characteristics of absorbing and releasing metal ions (such as lithium ions) is included. As positive electrode active materials, lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, transition metal oxynitrides, etc. can be cited. As lithium-containing transition metal oxides, Li(NiCoAl)O2, Li(NiCoMn)O2, LiCoO2, etc. can be cited. As a positive electrode active material, for example, when a lithium-containing transition metal oxide is used, the manufacturing cost of the electrode composition 2000 can be reduced, and the average discharge voltage of the battery can be increased. Li(NiCoAl)O2 means that Ni, Co and Al are contained in any proportion. Li(NiCoMn)O2 means that Ni, Co and Mn are contained in any proportion.

[0282] The median particle size of the positive electrode active material can be 0.1 μm or more and 100 μm or less, or 1 μm or more and 10 μm or less. When the median particle size of the positive electrode active material is 0.1 μm or more, in the electrode composition 2000, the active material 201 can be easily dispersed in the solvent 102. As a result, the charge and discharge characteristics of the battery using the electrode sheet manufactured by the electrode composition 2000 are improved. When the median particle size of the positive electrode active material is 100 μm or less, the lithium diffusion rate in the positive electrode active material is improved. Therefore, the battery can operate at high output.

[0283] The active material 201 includes a negative electrode active material. For example, as the negative electrode active material, a material having the characteristics of absorbing and releasing metal ions (such as lithium ions) is included. As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be mentioned. The metal material can be a single metal or an alloy. As the metal material, lithium metal, lithium alloy, etc. can be mentioned. As the carbon material, natural graphite, coke, carbon in the process of graphitization, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. can be mentioned. By using silicon (Si), tin (Sn), silicon compounds, tin compounds, etc., the capacity density of the battery can be increased. By using an oxide compound containing titanium (Ti) or niobium (Nb), the safety of the battery can be improved.

[0284] The median particle size of the negative electrode active material can be greater than 0.1 μm and less than 100 μm, or greater than 1 μm and less than 10 μm. When the median particle size of the negative electrode active material is greater than 0.1 μm, in the electrode composition 2000, the active material 201 can be easily dispersed in the solvent 102. As a result, the charge and discharge characteristics of the battery using the electrode sheet manufactured by the electrode composition 2000 are improved. When the median particle size of the negative electrode active material is less than 100 μm, the lithium diffusion rate in the negative electrode active material is increased. Therefore, the battery can operate at high output.

[0285] In order to reduce the interface resistance between each active material and the solid electrolyte, the positive electrode active material and the negative electrode active material can be coated with a coating material. That is, a coating layer can be set on the surface of the positive electrode active material and the negative electrode active material. The coating layer is a layer containing a coating material. As a coating material, a material with low electron conductivity can be used. As a coating material, an oxide material, an oxide solid electrolyte, a halide solid electrolyte, a sulfide solid electrolyte, etc. can be used. The positive electrode active material and the negative electrode active material can also be coated with only one coating material selected from the above materials. That is, a coating layer formed by only one coating material selected from the above materials can be set. Alternatively, two or more coating materials selected from the above materials can be used to set more than two coating layers.

[0286] Oxide materials used as the coating material include SiO2, Al2O3, TiO2, B2O3, Nb2O5, WO3, ZrO2 and the like.

[0287] As the oxide solid electrolyte used as the coating material, the oxide solid electrolyte exemplified in Embodiment 1 can be used. For example, Li-Nb-O compounds such as LiNbO3, Li-BO compounds such as LiBO2 and Li3BO3, Li-Al-O compounds such as LiAlO2, Li-Si-O compounds such as Li4SiO4, Li2SO4, Li4Ti5O 12 Li-Ti-O compounds, such as Li2ZrO3, Li-Zr-O compounds, such as Li2MoO3, Li-VO compounds, such as LiV2O5, Li-WO compounds, such as Li2WO4, Li-PO compounds, such as LiPO4, etc. Oxide solid electrolytes have high potential stability. Therefore, by using oxide solid electrolytes as coating materials, the cycle performance of the battery can be further improved.

[0288] As the halide solid electrolyte used as the coating material, the halide solid electrolyte exemplified in Embodiment 1 can be used. For example, Li-Y-Cl compounds such as LiYCl6, Li-Y-Br-Cl compounds such as LiYBr2Cl4, Li-Ta-O-Cl compounds such as LiTaOCl4, Li 2.7 Ti 0.3 Al 0.7 F6 and other Li-Ti-Al-F compounds. Halide solid electrolytes have high ion conductivity and high potential stability. Therefore, by using halide solid electrolytes as coating materials, the cycle performance of the battery can be further improved.

[0289] As the sulfide solid electrolyte used as the coating material, the sulfide solid electrolyte exemplified in Embodiment 1 can be used. For example, Li-PS compounds such as Li2S-P2S5 can be cited. Sulfide solid electrolytes have high ion conductivity and low Young's modulus. Therefore, by using a sulfide solid electrolyte as a coating material, uniform coating can be achieved, further improving the cycle performance of the battery.

[0290] <Electrode composition>

[0291] The electrode composition 2000 may be in a paste state or in a state of a dispersion liquid. The active material 201 and the ion conductor 111 are, for example, particles. In the manufacture of the electrode composition 2000, the particles of the active material 201 and the particles of the ion conductor 111 are mixed with the solvent 102. In the manufacture of the electrode composition 2000, there is no particular limitation on the mixing method of the active material 201, the ion conductor 111 and the solvent 102, that is, the mixing method of the active material 201, the solid electrolyte 101, the solvent 102, the binder 103 and the nitrogen-containing organic matter 104. For example, a mixing method using a mixing device such as a stirring type, a vibration type, an ultrasonic type, and a rotating type can be cited. For example, a mixing method using a high-speed homogenizer, a thin film rotating high-speed mixer, an ultrasonic homogenizer, a high-pressure homogenizer, a ball mill, a bead mill, a planetary mixer, a sand mill, a roller mill, a kneader and other dispersing and kneading devices can be cited. These mixing methods can be used alone or in combination of two or more.

[0292] [Method for producing electrode composition]

[0293] The electrode composition 2000 is manufactured, for example, by the following method. First, the active material 201 and the solvent 102 are mixed to prepare a dispersion. A solution containing a binder 103 and a solution containing a nitrogen-containing organic matter 104 are added to the obtained dispersion. The obtained mixed solution is subjected to high-speed shearing treatment using an online disperser and grinder. The solid electrolyte 101 is added to the obtained dispersion. The obtained mixed solution is subjected to high-speed shearing treatment using an online disperser and grinder. Through such a process, an ion conductor 111 is formed, and the active material 201 and the ion conductor 111 are dispersed and stabilized in the solvent 102, so that an electrode composition 2000 with better fluidity can be manufactured. The electrode composition 2000 can also be manufactured by mixing the solvent 102, the pre-made ion conductor 111, and the active material 201, and subjecting the obtained mixed solution to high-speed shearing treatment. The electrode composition 2000 can also be manufactured by mixing the pre-made solid electrolyte composition 1000 and the active material 201, and subjecting the obtained mixed solution to high-speed shearing treatment.

[0294] The electrode composition 2000 can be manufactured, for example, by the following method. First, the active material 201 and the solvent 102 are mixed, and then a solution containing a binder 103 and a solution containing a nitrogen-containing organic matter 104 are added. The obtained mixed solution is subjected to high shear treatment using an ultrasonic homogenizer. The solid electrolyte 101 is added to the obtained dispersion. The obtained mixed solution is subjected to high shear treatment using an ultrasonic homogenizer. Through such a process, an ion conductor 111 is formed, and the active material 201 and the ion conductor 111 are dispersed and stabilized in the solvent 102, so that an electrode composition 2000 with better fluidity can be manufactured. The electrode composition 2000 can also be manufactured by mixing a solvent 102, a pre-made ion conductor 111, and an active material 201, and subjecting the obtained mixed solution to high shear treatment using ultrasound. The electrode composition 2000 can also be manufactured by mixing a pre-made solid electrolyte composition 1000 and an active material 201, and subjecting the obtained mixed solution to high shear treatment using ultrasound.

[0295] From the perspective of manufacturing an electrode composition 2000 with improved fluidity, high-speed shear treatment or high-shear treatment using ultrasound can be carried out under conditions where no crushing of the particles of the solid electrolyte 101 and the particles of the active material 201 occurs and where fragmentation between the particles of the solid electrolyte 101 and between the particles of the active material 201 occurs.

[0296] In order to improve the electronic conductivity, the electrode composition 2000 may include a conductive additive. Examples of the conductive additive include graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black and Ketjen black, conductive fibers such as carbon fibers and metal fibers, conductive powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, conductive polymers such as polyaniline, polypyrrole, and polythiophene, etc. If a carbon material is used as the conductive additive, low cost can be achieved.

[0297] In the electrode composition 2000, the ratio of the mass of the ion conductor 111 to the mass of the active material 201 is not particularly limited, and may be, for example, 10% to 150% by mass, for example, 20% to 100% by mass, or 30% to 70% by mass. When the ratio of the mass of the ion conductor 111 is 10% to 100% by mass, the ion conductivity can be improved in the electrode composition 2000, and a high output of the battery can be achieved. When the ratio of the mass of the ion conductor 111 is 150% to 150% by mass, a high energy density of the battery can be achieved.

[0298] The solid content concentration of the electrode composition 2000 is appropriately determined according to the particle size of the active material 201, the specific surface area of ​​the active material 201, the particle size of the solid electrolyte 101, the specific surface area of ​​the solid electrolyte 101, the type of the solvent 102, the type of the binder 103, and the type of the nitrogen-containing organic matter 104. The solid content concentration of the electrode composition 2000 can be 40% by mass or more and 90% by mass or less, or 50% by mass or more and 80% by mass or less. By making the solid content concentration 40% by mass or more, the electrode composition 2000 has a desired viscosity, so it is easy to apply the electrode composition 2000 to a substrate such as an electrode. By making the solid content concentration 90% by mass or less, the wet film thickness when the electrode composition 2000 is applied to the substrate can be relatively thickened. Thus, an electrode sheet with a more uniform film thickness can be manufactured.

[0299] The electrode composition 2000 may include an aminohydroxy compound as the nitrogen-containing organic material 104. As described above, the nitrogen-containing organic material 104 can further improve the dispersibility of the solid electrolyte 101 and the active material 201 such as the lithium-containing transition metal oxide and the oxide containing titanium (Ti) or niobium (Nb).

[0300] The flowability of the electrode composition 2000 can be evaluated by evaluating rheological properties using a viscosity / viscoelasticity measuring device.

[0301] In the electrode composition 2000, the rheological properties can be evaluated based on the Casson yield value obtained in the speed control mode using a viscosity and viscoelasticity measuring device. The Casson yield value can be calculated by the above method. In the electrode composition 2000, the Casson yield value can be greater than 0.05Pa and less than 4.5Pa, or greater than 2.0Pa and less than 4.5Pa. By making the Casson yield value greater than 0.05Pa, it is easy to apply the electrode composition 2000 on a substrate. By making the Casson yield value less than 4.5Pa, a coating film with a more uniform thickness can be manufactured.

[0302] In the electrode composition 2000 , rheological properties can be evaluated based on the storage elastic modulus G′ and the loss tangent tan δ obtained in a strain control mode using a viscosity / viscoelasticity measuring device.

[0303] The loss tangent tanδ can be measured by the above method. In the electrode composition 2000, the loss tangent tanδ when γ=0.1% can be greater than 0.30 and less than 5.0, or greater than 0.50 and less than 1.0. By making the loss tangent tanδ when γ=0.1% less than 5.0, it is easy to apply the electrode composition 2000 to a substrate, etc. As a result, in the coating obtained using the electrode composition 2000, the uniformity of the film thickness can be improved. By making the loss tangent tanδ when γ=0.1% greater than 0.30, when the electrode composition 2000 is applied to a substrate, etc., the electrode composition 2000 is easy to wet and spread. As a result, the uniformity of the film thickness of the electrode sheet can be further improved.

[0304] (Implementation method 3)

[0305] Embodiment 3 will be described below. The description overlapping with that of Embodiment 1 or Embodiment 2 will be omitted as appropriate.

[0306] The solid electrolyte sheet in Embodiment 3 is produced using the solid electrolyte composition 1000. The method for producing the solid electrolyte sheet includes applying the solid electrolyte composition 1000 on an electrode or a substrate to form a coating film, and removing the solvent from the coating film.

[0307] Below, refer to Figure 4 A method for producing a solid electrolyte sheet will be described. Figure 4 This is a flow chart showing a method for producing a solid electrolyte sheet.

[0308] The method for manufacturing a solid electrolyte sheet may include step S01 , step S02 , and step S03 . Figure 4 The step S01 in corresponds to the method for manufacturing the solid electrolyte composition 1000 described in Embodiment 1. The method for manufacturing a solid electrolyte sheet includes a step S02 of applying the solid electrolyte composition 1000 in Embodiment 1 and a step S03 of drying. Step S01, step S02, and step S03 can be implemented in this order. Through the above steps, a homogeneous solid electrolyte sheet having a uniform thickness can be manufactured over a large area and efficiently using the solid electrolyte composition 1000. In this way, the solid electrolyte sheet is obtained by applying the solid electrolyte composition 1000 and drying it. In other words, the solid electrolyte sheet is a solidified product of the solid electrolyte composition 1000.

[0309] Figure 5 3 is a cross-sectional view of an electrode assembly 3001 in Embodiment 3. The electrode assembly 3001 includes an electrode 4001 and a solid electrolyte sheet 301 disposed on the electrode 4001. By including a step of applying a solid electrolyte composition 1000 on the electrode 4001 as step S02, the electrode assembly 3001 can be manufactured.

[0310] Figure 6 3 is a cross-sectional view of a transfer sheet 3002 in Embodiment 3. The transfer sheet 3002 includes a substrate 302 and a solid electrolyte sheet 301 disposed on the substrate 302. By including a step of applying a solid electrolyte composition 1000 on the substrate 302 as step S02, the transfer sheet 3002 can be manufactured.

[0311] In step S02 , the solid electrolyte composition 1000 is applied to the electrode 4001 or the substrate 302 . Thus, a coating film of the solid electrolyte composition 1000 is formed on the electrode 4001 or the substrate 302 .

[0312] The electrode 4001 is a positive electrode or a negative electrode. The positive electrode or the negative electrode includes a current collector and an active material layer disposed on the current collector. The solid electrolyte composition 1000 is applied to the electrode 4001, and the electrode assembly 3001 consisting of a stack of the electrode 4001 and the solid electrolyte sheet 301 is manufactured through step S03 described below.

[0313] As the material used for the substrate 302, metal foil and resin film can be cited. As the material of the metal foil, copper (Cu), aluminum (Al), iron (Fe), nickel (Ni), their alloys, etc. can be cited. As the material of the resin film, polyethylene terephthalate (PET), polyimide (PI), polytetrafluoroethylene (PTFE), etc. can be cited. The solid electrolyte composition 1000 is applied to the substrate 302, and after the step S03 described later, the transfer sheet 3002 consisting of the laminate of the substrate 302 and the solid electrolyte sheet 301 is manufactured.

[0314] Examples of the coating method include die coating, gravure coating, blade coating, rod coating, spray coating, and electrostatic coating. From the viewpoint of mass productivity, coating can be performed by die coating.

[0315] In step S03, the solid electrolyte composition 1000 applied on the electrode 4001 or the substrate 302 is dried. By drying the solid electrolyte composition 1000, for example, the solvent 102 is removed from the coating film of the solid electrolyte composition 1000, so that the solid electrolyte sheet 301 is produced.

[0316] Examples of drying methods for removing the solvent 102 from the solid electrolyte composition 1000 include warm air / hot air drying, infrared heating drying, reduced pressure drying, vacuum drying, high-frequency dielectric heating drying, and high-frequency induction heating drying. These methods may be used alone or in combination of two or more.

[0317] The solvent 102 can be removed from the solid electrolyte composition 1000 by drying under reduced pressure. That is, the solvent 102 can be removed from the solid electrolyte composition 1000 in a pressure atmosphere lower than atmospheric pressure. The pressure atmosphere lower than atmospheric pressure can be, for example, -0.01 MPa or less in gauge pressure. The reduced pressure drying can be performed at 50° C. or higher and 250° C. or lower.

[0318] The solvent 102 can be removed from the solid electrolyte composition 1000 by vacuum drying. That is, the solvent 102 can be removed from the solid electrolyte composition 1000 in an atmosphere at a temperature lower than the boiling point of the solvent 102 and below the equilibrium vapor pressure of the solvent 102 .

[0319] From the viewpoint of production cost, the solvent 102 can be removed from the solid electrolyte composition 1000 by warm air or hot air drying. The setting temperature of the warm air or hot air may be 50° C. to 250° C., or 80° C. to 150° C.

[0320] In step S03, a part or all of the nitrogen-containing organic matter 104 may be removed simultaneously with the removal of the solvent 102. By removing the nitrogen-containing organic matter 104, the ion conductivity of the solid electrolyte sheet 301 and the strength of the coating film can be improved.

[0321] In step S03, the nitrogen-containing organic substance 104 may not be removed at the same time as the solvent 102. By leaving the nitrogen-containing organic substance 104 in the solid electrolyte sheet 301, the nitrogen-containing organic substance 104 acts like lubricant during press molding in the manufacture of the battery. This can improve the filling property of the ion conductor 111.

[0322] In step S03 , the amount of the solvent 102 and the amount of the nitrogen-containing organic matter 104 removed from the solid electrolyte composition 1000 can be adjusted by the above-mentioned drying method and drying conditions.

[0323] The removal of the solvent 102 and the nitrogen-containing organic matter 104 can be confirmed, for example, by Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), gas chromatography (GC) or gas chromatography-mass spectrometry (GC / MS). In addition, as long as the solid electrolyte sheet 301 after drying has ion conductivity, the solvent 102 may not be completely removed. A portion of the solvent 102 may remain on the solid electrolyte sheet 301.

[0324] The ion conductivity of the solid electrolyte sheet 301 may be 0.1 mS / cm or more, or 1 mS / cm or more. By setting the ion conductivity to 0.1 mS / cm or more, the output characteristics of the battery can be improved. In addition, in order to improve the ion conductivity of the solid electrolyte sheet 301, a press machine or the like may be used for press molding.

[0325] (Implementation 4)

[0326] Embodiment 4 will be described below. The description overlapping with Embodiments 1 to 3 will be appropriately omitted.

[0327] The electrode sheet in Embodiment 4 is manufactured using the electrode composition 2000. The method for manufacturing the electrode sheet in Embodiment 4 includes: applying the electrode composition 2000 on a current collector, a substrate, or an electrode assembly to form a coating film, and removing the solvent from the coating film.

[0328] The method for manufacturing the electrode sheet is the same as the method for manufacturing the solid electrolyte sheet 301 described in the third embodiment, except that the substrate in the manufacturing of the solid electrolyte sheet 301 described in the third embodiment is partially different. Figure 4 The method for manufacturing the electrode sheet is described below. Figure 4 It also corresponds to a flow chart showing a method for manufacturing an electrode sheet.

[0329] The method for manufacturing an electrode sheet may include step S01 , step S02 , and step S03 . Figure 4 The process S01 in the embodiment corresponds to the method for manufacturing the electrode composition 2000 described in the second embodiment. The method for manufacturing the electrode sheet includes a process S02 for coating the electrode composition 2000 in the second embodiment and a process S03 for drying. The process S01, the process S02 and the process S03 can be implemented in this order. Through the above process, using the electrode composition 2000, it is possible to manufacture a homogeneous electrode sheet with uniform thickness over a large area and with high efficiency. In this way, the electrode sheet is obtained by coating the electrode composition 2000 and drying it. In other words, the electrode sheet is a solidified product of the electrode composition 2000.

[0330] Figure 7 4 is a cross-sectional view of an electrode 4001 in Embodiment 4. Electrode 4001 includes a current collector 402 and an electrode sheet 401 disposed on current collector 402. Electrode 4001 can be manufactured by including a step of applying electrode composition 2000 on current collector 402 as step S02.

[0331] Figure 84 is a cross-sectional view of an electrode transfer sheet 4002 in Embodiment 4. The electrode transfer sheet 4002 includes a substrate 302 and an electrode sheet 401 disposed on the substrate 302. As a material used for the substrate 302, the materials exemplified in Embodiment 3 and the like can be used. By including a step of applying the electrode composition 2000 on the substrate 302 as step S02, the electrode transfer sheet 4002 consisting of a laminate of the substrate 302 and the electrode sheet 401 can be manufactured.

[0332] Fig. 9 4 is a cross-sectional view of a battery precursor 4003 in Embodiment 4. The battery precursor 4003 includes an electrode 4001, an electrolyte layer 502, and an electrode sheet 403. The electrolyte layer 502 is arranged on the electrode 4001. In addition, the electrode sheet 403 is arranged on the electrolyte layer 502. The electrode 4001 includes a current collector 402 and an electrode sheet 401 arranged on the current collector 402. The electrode assembly 3001 includes the electrode 4001 and the electrolyte layer 502 arranged on the electrode 4001. The electrolyte layer 502 includes a solid electrolyte sheet 301. As step S02, the battery precursor 4003 can be manufactured by a step of applying the electrode composition 2000 on the electrode assembly 3001, which is a laminate of the electrode 4001 and the electrolyte layer 502.

[0333] In step S02, the electrode composition 2000 is applied onto the current collector 402, the substrate 302, or the electrode assembly 3001. Thus, a coating film of the electrode composition 2000 is formed on the current collector 402, the substrate 302, or the electrode assembly 3001.

[0334] Examples of the coating method include die coating, gravure coating, blade coating, rod coating, spray coating, and electrostatic coating. From the viewpoint of mass productivity, coating can be performed by die coating.

[0335] As the material used for the current collector 402, metal foil can be cited. As the material of the metal foil, copper (Cu), aluminum (Al), iron (Fe), nickel (Ni), their alloys, etc. can be cited. A coating layer consisting of the above-mentioned conductive auxiliary agent and the above-mentioned binder can be provided on the surface of these metal foils. The electrode composition 2000 is applied to the current collector 402, and the electrode 4001 consisting of the laminate of the current collector 402 and the electrode sheet 401 is manufactured through the step S03 described later.

[0336] Next, the electrolyte layer 502 is formed on the electrode 4001. The method for forming the electrolyte layer 502 is as described in Embodiment 3. That is, the solid electrolyte composition 1000 is applied to the electrode 4001, and the electrolyte layer 502 is formed on the electrode 4001 through step S03. In this way, the electrode assembly 3001 composed of the stacked body of the electrode 4001 and the electrolyte layer 502 is manufactured.

[0337] In step S03, the applied solid electrolyte composition 1000 is dried. By drying the solid electrolyte composition 1000, for example, the solvent 102 is removed from the coating film of the solid electrolyte composition 1000, thereby producing the electrolyte layer 502.

[0338] Then, the electrode sheet 403 is formed on the electrolyte layer 502. The method for forming the electrode sheet 403 is, for example, the same as the method for forming the electrode sheet 401. That is, the electrode composition 2000 is applied on the electrolyte layer 502, and the electrode sheet 403 is formed on the electrolyte layer 502 through step S03.

[0339] In step S03, the applied electrode composition 2000 is dried. By drying the electrode composition 2000, for example, the solvent 102 is removed from the coating film of the electrode composition 2000, thereby manufacturing the electrode sheet 403.

[0340] The drying process for removing the solvent 102 from the electrode composition 2000 is as described in the third embodiment.

[0341] The battery precursor 4003 can be manufactured, for example, by combining the electrode 4001 and the electrode sheet 403 having a polarity opposite to that of the electrode 4001. That is, the active material contained in the electrode sheet 401 is different from the active material contained in the electrode sheet 403. In detail, when the active material contained in the electrode sheet 401 is a positive electrode active material, the active material contained in the electrode sheet 403 is a negative electrode active material. When the active material contained in the electrode sheet 401 is a negative electrode active material, the active material contained in the electrode sheet 403 is a positive electrode active material.

[0342] (Implementation 5)

[0343] Embodiment 5 will be described below, and descriptions overlapping with those of Embodiments 1 to 4 will be omitted as appropriate.

[0344] Fig.10 This is a cross-sectional view of a battery 5000 in the fifth embodiment.

[0345] The battery 5000 in the fifth embodiment includes a positive electrode 501 , a negative electrode 503 , and an electrolyte layer 502 .

[0346] The electrolyte layer 502 is disposed between the positive electrode 501 and the negative electrode 503 .

[0347] The electrolyte layer 502 may include the solid electrolyte sheet 301 in the third embodiment, and either the positive electrode 501 or the negative electrode 503 may include the electrode sheet 401 in the fourth embodiment.

[0348] The battery 5000 may include a homogeneous solid electrolyte sheet 301 having a uniform thickness. The homogeneous solid electrolyte sheet 301 having a uniform thickness means that the thickness deviation of the solid electrolyte sheet 301 is small. The solid electrolyte sheet 301 with a small thickness deviation can have a thickness close to the design value at all positions in the surface. Therefore, even when the electrolyte layer 502 is made thinner, the possibility of contact (short circuit) between the positive electrode 501 and the negative electrode 503 can be reduced, and the energy density of the battery 5000 can be improved. As a result, a high-performance battery 5000 can be manufactured over a large area and efficiently.

[0349] The battery 5000 may include a homogeneous electrode sheet 401 having a uniform thickness. The homogeneous electrode sheet 401 having a uniform thickness means that the thickness deviation of the electrode sheet 401 is small. The electrode sheet 401 having a small thickness deviation can have a thickness close to the design value at all positions in the surface. Therefore, during the operation of the battery 5000, a uniform reaction can be achieved at the positive electrode and the negative electrode, thereby improving the cycle characteristics of the battery 5000. Thus, a high-performance battery 5000 can be manufactured over a large area and with high efficiency.

[0350] In the battery 5000, at least one selected from the positive electrode 501 and the negative electrode 503 can be the electrode 4001. The battery 5000 can be manufactured, for example, by combining the electrode 4001 and an electrode having a polarity opposite to that of the electrode 4001. This method is excellent from the perspective of reducing the number of components. When the electrode 4001 is a positive electrode, the electrode having a polarity opposite to that of the electrode 4001 is a negative electrode. When the electrode 4001 is a negative electrode, the electrode having a polarity opposite to that of the electrode 4001 is a positive electrode. The positive electrode or the negative electrode includes a current collector and an active material layer disposed on the current collector. A layer including a solid electrolyte can be provided on the active material layer of the positive electrode or the active material layer of the negative electrode.

[0351] As a method for manufacturing the battery 5000, a transfer method and a coating method can be cited. The transfer method is a method for manufacturing the battery 5000 using the transfer sheet 3002 and the electrode transfer sheet 4002. That is, the transfer method is a method for manufacturing the battery 5000 by making each component of the battery 5000 by a separate process and then combining these components. The coating method is, for example, a method for manufacturing the battery 5000 including a method of directly forming an electrolyte layer on the positive electrode or the negative electrode by coating the solid electrolyte composition 1000 on the positive electrode or the negative electrode and drying it.

[0352] An example of a method for manufacturing the battery 5000 using the transfer method is described below.

[0353] In the battery 5000, the electrolyte layer 502 can be manufactured using the transfer sheet 3002. In this case, first, the solid electrolyte sheet 301 is transferred from the transfer sheet 3002 to the first electrode. Then, the battery 5000 can be manufactured by combining the first electrode, the second electrode, and the electrolyte layer 502 in such a manner that the electrolyte layer 502 including the transferred solid electrolyte sheet 301 is arranged between the first electrode and the second electrode. That is, the manufacturing method of the battery 5000 includes: applying the solid electrolyte composition 1000 on the substrate 302 to form a coating film; and removing the solvent 102 from the coating film to form the electrolyte layer 502. In addition, the manufacturing method of the battery 5000 includes: combining the first electrode, the second electrode, and the electrolyte layer 502 in such a manner that the electrolyte layer 502 is located between the first electrode and the second electrode. As a result, the battery 5000 having the first electrode, the electrolyte layer, and the second electrode in sequence is obtained. The electrolyte layer 502 includes the solid electrolyte sheet 301. That is, the electrolyte layer 502 includes a solidified material of the solid electrolyte composition 1000. In order to transfer the solid electrolyte sheet 301 from the transfer sheet 3002 to the first electrode, the transfer sheet 3002 is arranged on the first electrode in such a manner that the solid electrolyte sheet 301 contacts the first electrode, and then the substrate 302 is removed. Thus, the solid electrolyte sheet 301 is transferred to the first electrode. Then, the second electrode is arranged on the solid electrolyte sheet 301 in such a manner that the solid electrolyte sheet 301 contacts the second electrode. Thus, the battery 5000 is manufactured. When the solid electrolyte sheet 301 and the second electrode are combined, an electrode transfer sheet 4002 including the second electrode can be used. When the first electrode is a positive electrode, the second electrode is a negative electrode. When the first electrode is a negative electrode, the second electrode is a positive electrode. The positive electrode and the negative electrode include a current collector and an active material layer arranged on the current collector. A layer including a solid electrolyte can be provided on the active material layer of the positive electrode or the active material layer of the negative electrode.

[0354] The battery 5000 can be manufactured using the electrode transfer sheet 4002 in Embodiment 4. In this case, first, the electrode sheet 401 is transferred from the electrode transfer sheet 4002 to the electrolyte layer 502. Next, the current collector 402 is combined with the transferred electrode sheet 401. The stack of the electrode sheet 401 and the current collector 402 is defined as the first electrode. Then, the battery 5000 can be manufactured by combining the second electrode having a polarity opposite to that of the first electrode in such a manner that the electrolyte layer 502 is arranged between the first electrode and the second electrode. That is, the method for manufacturing the battery 5000 includes: applying the electrode composition 2000 on the substrate 302 to form a coating film; and removing the solvent 102 from the coating film to form the electrode sheet 401 for the first electrode. In addition, the method for manufacturing the battery 5000 includes: combining the first electrode, the second electrode and the electrolyte layer 502 in such a manner that the electrolyte layer 502 is located between the first electrode and the second electrode. Thus, a battery 5000 having a first electrode, an electrolyte layer, and a second electrode in sequence is obtained. As described above, the first electrode includes an electrode sheet 401. That is, the first electrode includes a solidified product of the electrode composition 2000. The second electrode may also include a solidified product of the electrode composition 2000. In order to transfer the electrode sheet 401 from the electrode transfer sheet 4002 to the electrolyte layer 502, the electrode transfer sheet 4002 is arranged on the electrolyte layer 502 in such a manner that the electrode sheet 401 contacts the electrolyte layer 502, and then the substrate 302 is removed. Thus, the electrode sheet 401 is transferred to the electrolyte layer 502. Next, the collector 402 is combined with the transferred electrode sheet 401. Then, the second electrode is arranged on the electrolyte layer 502 in such a manner that the electrolyte layer 502 contacts the second electrode. Thus, a battery 5000 is manufactured. When the first electrode is a positive electrode, the second electrode is a negative electrode. When the first electrode is a negative electrode, the second electrode is a positive electrode. The positive electrode and the negative electrode include a current collector and an active material layer disposed on the current collector.

[0355] The battery 5000 can be manufactured using the transfer sheet 3002 and the electrode transfer sheet 4002. In this case, first, the electrode sheet 401 is transferred from the electrode transfer sheet 4002 to the current collector 402. Thus, the electrode 4001 consisting of a laminate of the current collector 402 and the electrode sheet 401 is obtained. The electrode 4001 is, for example, the first electrode. Next, the solid electrolyte sheet 301 is transferred from the transfer sheet 3002 to the first electrode. In detail, the solid electrolyte sheet 301 is transferred to the electrode sheet 401. Thus, the electrode assembly 3001, which is a laminate of the electrode 4001 and the solid electrolyte sheet 301, is obtained. Then, by combining the electrode assembly 3001 and the second electrode, the battery 5000 can be manufactured. When combining the electrode assembly 3001 and the second electrode, the electrode transfer sheet 4002 including the second electrode can be used. That is, the manufacturing method of the battery 5000 includes: applying the electrode composition 2000 on the first substrate to form a first coating film; and removing the solvent 102 from the first coating film to form the first electrode. In addition, the manufacturing method of the battery 5000 includes: applying the solid electrolyte composition 1000 on the second substrate to form a second coating film; and removing the solvent 102 from the second coating film to form the electrolyte layer 502. In addition, the manufacturing method of the battery 5000 includes: combining the first electrode, the second electrode and the electrolyte layer 502 in a manner that the electrolyte layer 502 is located between the first electrode and the second electrode. Thus, the battery 5000 having the first electrode, the electrolyte layer and the second electrode in sequence is obtained. At least one selected from the first electrode and the second electrode includes the electrode sheet 401. That is, at least one selected from the first electrode and the second electrode includes a solidified product of the electrode composition 2000. The electrolyte layer 502 includes a solid electrolyte sheet 301. That is, the electrolyte layer includes a solidified product of the solid electrolyte composition 1000.

[0356] In the method for manufacturing battery 5000, when transfer sheet 3002 is used, solid electrolyte sheet 301, positive electrode and negative electrode are manufactured by separate processes. Therefore, in manufacturing battery 5000, there is no need to consider the influence of the solvent used in manufacturing solid electrolyte sheet 301 on the positive electrode and negative electrode. Therefore, various solvents can be used in manufacturing solid electrolyte sheet 301.

[0357] In the manufacturing method of the battery 5000, when the electrode transfer sheet 4002 is used, the electrode sheet 401 and the electrolyte layer 502 are manufactured by separate processes. Therefore, in the manufacturing of the battery 5000, it is not necessary to consider the influence of the solvent used in the manufacturing of the electrode sheet 401 on the electrolyte layer 502. Therefore, various solvents can be used in the manufacturing of the electrode sheet 401.

[0358] A method for manufacturing the battery 5000 using a coating method is described below.

[0359] The manufacturing method of the battery 5000 includes, for example, applying the solid electrolyte composition 1000 on the first electrode to form a coating film; and removing the solvent 102 from the coating film to form an electrode assembly 3001 including a laminate of the first electrode and the electrolyte layer 502. In addition, the manufacturing method of the battery 5000 includes combining the first electrode, the second electrode, and the electrolyte layer 502 in such a manner that the electrolyte layer 502 is located between the first electrode and the second electrode. In this way, a battery 5000 having the first electrode, the electrolyte layer, and the second electrode in sequence can be obtained. The electrolyte layer 502 includes a solid electrolyte sheet 301. For example, by configuring the second electrode on the solid electrolyte sheet 301, the battery 5000 can be obtained. As a method for configuring the second electrode on the solid electrolyte sheet 301, a method of applying the electrode composition 2000 on the solid electrolyte sheet 301, a method of transferring the electrode sheet or the second electrode to the solid electrolyte sheet 301, and the like can be cited. When the first electrode is a positive electrode, the second electrode is a negative electrode. When the first electrode is a negative electrode, the second electrode is a positive electrode. The first electrode and the second electrode each include, for example, a current collector and an active material layer disposed on the current collector. A layer including a solid electrolyte may be provided on the active material layer of the first electrode or the active material layer of the second electrode.

[0360] The manufacturing method of the battery 5000 includes, for example, applying the electrode composition 2000 on the current collector 402 to form a coating film; and removing the solvent 102 from the coating film to form the first electrode. In addition, the manufacturing method of the battery 5000 includes: combining the first electrode, the second electrode and the electrolyte layer 502 in a manner that the electrolyte layer 502 is located between the first electrode and the second electrode. As a result, the battery 5000 having the first electrode, the electrolyte layer and the second electrode in sequence is obtained. The electrolyte layer 502 includes a solid electrolyte sheet 301. For example, the battery 5000 is obtained by configuring the second electrode on the solid electrolyte sheet 301. As a method for configuring the second electrode on the solid electrolyte sheet 301, a method of applying the electrode composition 2000 on the solid electrolyte sheet 301, a method of transferring the electrode sheet or the second electrode to the solid electrolyte sheet 301, etc. can be cited. When the first electrode is a positive electrode, the second electrode is a negative electrode. When the first electrode is a negative electrode, the second electrode is a positive electrode. The first electrode and the second electrode each include, for example, a current collector and an active material layer disposed on the current collector. A layer including a solid electrolyte may be provided on the active material layer of the first electrode or the active material layer of the second electrode.

[0361] The manufacturing method of the battery 5000 includes, for example, applying the electrode composition 2000 on the electrode assembly 3001 to form a coating film; and removing the solvent from the coating film to form an electrode sheet 403 for the second electrode. The second electrode is produced by combining the current collector 402 on the electrode sheet 403 to obtain the battery 5000. Thus, the battery 5000 having the first electrode, the electrolyte layer and the second electrode in sequence is obtained. The electrode assembly 3001 includes the electrode 4001 and the electrolyte layer 502. The electrode 4001 is, for example, the first electrode. The electrolyte layer 502 includes the solid electrolyte sheet 301.

[0362] The manufacturing method of the battery 5000 includes, for example, applying the electrode composition 2000 on the current collector 402 to form a first coating film; and removing the solvent from the first coating film to form a first electrode. In addition, the manufacturing method of the battery 5000 includes: applying the solid electrolyte composition 1000 on the first electrode to form a second coating film; and removing the solvent from the second coating film to form an electrolyte layer 502. In addition, the manufacturing method of the battery 5000 includes: combining the first electrode, the second electrode, and the electrolyte layer 502 in a manner such that the electrolyte layer 502 is located between the first electrode and the second electrode. In detail, the battery 5000 can be obtained by applying the electrode composition 2000 including the second electrode on the electrolyte layer 502 including the solid electrolyte sheet 301 to form a third coating film, and removing the solvent from the third coating film to form a second electrode including an electrode sheet. In this way, the battery 5000 having the first electrode, the electrolyte layer, and the second electrode in sequence is obtained.

[0363] These coating methods are superior in reducing the number of parts compared to the transfer method of transferring the solid electrolyte sheet 301 formed on the substrate 302 and the electrode sheet 401 formed on the substrate 302. In other words, the above methods are superior in mass productivity compared to the transfer method.

[0364] The battery 5000 can be manufactured by using the above method to make a stacked body in which a positive electrode, an electrolyte layer, and a negative electrode are sequentially arranged, and then press-molding the stacked body at room temperature or high temperature using a punching machine. Press-molding can improve the filling properties of the active material 201 and the ion conductor 111, thereby achieving high output of the battery 5000.

[0365] Battery 5000 can be manufactured by the following method. A negative electrode having an electrode sheet (first negative electrode sheet) stacked on a current collector, a first electrolyte layer, and a first positive electrode are arranged in this order. An electrode sheet (second negative electrode sheet), a second electrolyte layer, and a second positive electrode are sequentially arranged on the surface opposite to the surface of the current collector having the first negative electrode sheet stacked thereon. Thus, a stacked body having the first positive electrode, the first electrolyte layer, the first negative electrode sheet, the current collector, the second negative electrode sheet, the second electrolyte layer, and the second positive electrode sequentially arranged thereon is obtained. Battery 5000 can be manufactured by press-molding the stacked body at room temperature or high temperature using a punching machine. By such a method, a stacked body of two batteries 5000 can be manufactured while suppressing the warping of the battery, and a high-output battery 5000 can be manufactured more efficiently. In addition, in the manufacture of the stacked body, there is no particular limitation on the order in which the components are stacked. For example, after placing the first negative electrode sheet and the second negative electrode sheet on the current collector, the first electrolyte layer, the second electrolyte layer, the first positive electrode, and the second positive electrode may be placed in order to produce a stack of two batteries 5000 .

[0366] The electrolyte layer 502 is a layer containing an electrolyte material. As the electrolyte material, for example, a solid electrolyte can be cited. That is, the electrolyte layer 502 can be a solid electrolyte layer. As the solid electrolyte contained in the electrolyte layer 502, the solid electrolyte exemplified as the solid electrolyte 101 in Embodiment 1 can be used. As the solid electrolyte, for example, a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, a complex hydride solid electrolyte, etc. can be used.

[0367] The electrolyte layer 502 may contain a solid electrolyte as a main component. The electrolyte layer 502 may contain a solid electrolyte in an amount of 70% or more (70% by mass or more) relative to the entire electrolyte layer 502 by mass.

[0368] According to the above technical configuration, the output characteristics of the battery 5000 can be further improved.

[0369] The electrolyte layer 502 may contain a solid electrolyte as a main component and may further contain inevitable impurities. Examples of the inevitable impurities include starting materials, by-products, and decomposition products used when synthesizing the solid electrolyte.

[0370] The electrolyte layer 502 may contain a solid electrolyte in an amount of 100% by mass relative to the entire electrolyte layer 502 excluding impurities that are inevitably mixed therein.

[0371] According to the above technical configuration, the output characteristics of the battery 5000 can be further improved.

[0372] The electrolyte layer 502 may include two or more of the materials listed as the solid electrolyte. For example, the electrolyte layer 502 may include a halide solid electrolyte and a sulfide solid electrolyte.

[0373] The electrolyte layer 502 may be a layer produced by laminating a layer using the solid electrolyte sheet 301 and a layer containing a solid electrolyte having a composition different from that of the solid electrolyte 101 contained in the solid electrolyte sheet 301. The electrolyte layer 502 may be a single layer composed of the solid electrolyte sheet 301, or may be two or more layers composed of other solid electrolytes.

[0374] The electrolyte layer 502 may include a layer disposed between the layer using the solid electrolyte sheet 301 and the negative electrode 503, and including a solid electrolyte having a lower reduction potential than the solid electrolyte 101 contained in the solid electrolyte sheet 301. According to the above technical configuration, the reduction decomposition of the solid electrolyte 101 caused by the contact between the solid electrolyte 101 and the negative electrode active material can be suppressed, so that the output characteristics of the battery 5000 can be improved. As a solid electrolyte having a lower reduction potential than the solid electrolyte 101, for example, a sulfide solid electrolyte can be cited.

[0375] The thickness of the electrolyte layer 502 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 502 is 1 μm or more, the possibility of a short circuit between the positive electrode 501 and the negative electrode 503 is reduced. When the thickness of the electrolyte layer 502 is 300 μm or less, the battery 5000 can easily operate at high output. That is, if the thickness of the electrolyte layer 502 is appropriately adjusted, the safety of the battery 5000 can be fully ensured, and the battery 5000 can operate at high output.

[0376] The thickness of the solid electrolyte sheet 301 contained in the electrolyte layer 502 may be 1 μm or more and 30 μm or less, 1 μm or more and 15 μm or less, or 1 μm or more and 7.5 μm or less. When the thickness of the solid electrolyte sheet 301 is 1 μm or more, the possibility of short circuit between the positive electrode 501 and the negative electrode 503 is reduced. When the thickness of the solid electrolyte sheet 301 is 30 μm or less, the internal resistance of the battery 5000 is reduced, and the battery 5000 can be operated at a high output, and the energy density of the battery 5000 can be increased. The thickness of the solid electrolyte sheet 301 is defined, for example, by the average value of any plurality of points (for example, 3 points) in a cross section parallel to the thickness direction.

[0377] There is no particular limitation on the shape of the solid electrolyte contained in the battery 5000. The solid electrolyte may be in a needle shape, a sphere shape, an ellipsoidal sphere shape, etc. The solid electrolyte may be in a particle shape.

[0378] At least one selected from the positive electrode 501 and the negative electrode 503 may include an electrolyte material, for example, a solid electrolyte. As the solid electrolyte, the solid electrolyte exemplified as the material constituting the electrolyte layer 502 can be used. According to the above technical configuration, the ion conductivity (for example, lithium ion conductivity) inside the positive electrode 501 or the negative electrode 503 is improved, and the battery 5000 can be operated at high output.

[0379] In the positive electrode 501 or the negative electrode 503 , a sulfide solid electrolyte can be used as the solid electrolyte, and the above-mentioned halide solid electrolyte can be used as the coating material that coats the active material.

[0380] The positive electrode 501 includes, for example, a material having a property of storing and releasing metal ions (for example, lithium ions) as a positive electrode active material. As the positive electrode active material, the materials exemplified in Embodiment 2 can be used.

[0381] When the solid electrolyte contained in the positive electrode 501 is in the form of particles (e.g., spheres), the median particle size of the solid electrolyte may be 100 μm or less. When the median particle size of the solid electrolyte is 100 μm or less, the positive electrode active material and the solid electrolyte can be well dispersed in the positive electrode 501. As a result, the charge and discharge characteristics of the battery 5000 are improved.

[0382] The median particle size of the solid electrolyte contained in the positive electrode 501 may be smaller than the median particle size of the positive electrode active material. This allows the solid electrolyte and the positive electrode active material to be well dispersed.

[0383] The median particle size of the positive electrode active material can be greater than 0.1 μm and less than 100 μm. When the median particle size of the positive electrode active material is greater than 0.1 μm, the positive electrode active material and the solid electrolyte can be well dispersed in the positive electrode 501. As a result, the charge and discharge characteristics of the battery 5000 are improved. When the median particle size of the positive electrode active material is less than 100 μm, the lithium diffusion rate in the positive electrode active material is increased. Therefore, the battery 5000 can operate at high output.

[0384] In the positive electrode 501, the volume ratio "v1:100-v1" of the positive electrode active material and the solid electrolyte can satisfy 30≤v1≤95. v1 represents the volume ratio of the positive electrode active material when the total volume of the positive electrode active material and the solid electrolyte contained in the positive electrode 501 is set to 100. When 30≤v1 is satisfied, it is easy to ensure sufficient energy density for the battery 5000. When v1≤95 is satisfied, it is easier for the battery 5000 to work at high output.

[0385] The thickness of the positive electrode 501 may be greater than 10 μm and less than 500 μm. When the thickness of the positive electrode 501 is greater than 10 μm, sufficient energy density can be easily ensured for the battery 5000. When the thickness of the positive electrode 501 is less than 500 μm, the battery 5000 can more easily operate at high output.

[0386] In the case where the positive electrode 501 includes the electrode sheet 401, the thickness of the electrode sheet 401 may be greater than 10 μm and less than 500 μm, or may be greater than 20 μm and less than 200 μm. When the thickness of the electrode sheet 401 is greater than 10 μm, the energy density of the battery 5000 can be increased. When the thickness of the electrode sheet 401 is less than 500 μm, the internal resistance of the battery 5000 is reduced, and operation at high output can be performed. The thickness of the electrode sheet 401 is defined, for example, by the average value of any multiple points (e.g., 3 points) in a cross section parallel to the thickness direction.

[0387] The negative electrode 503 includes, for example, a material having a property of storing and releasing metal ions (for example, lithium ions) as a negative electrode active material. As the negative electrode active material, the materials exemplified in Embodiment 2 can be used.

[0388] The median particle size of the negative electrode active material can be greater than 0.1 μm and less than 100 μm. When the median particle size of the negative electrode active material is greater than 0.1 μm, the negative electrode active material and the solid electrolyte can be well dispersed in the negative electrode 503. As a result, the charge and discharge characteristics of the battery 5000 are improved. When the median particle size of the negative electrode active material is less than 100 μm, the lithium diffusion rate in the negative electrode active material is increased. Therefore, the battery 5000 can operate at high output.

[0389] The median particle size of the negative electrode active material may be larger than the median particle size of the solid electrolyte, thereby allowing the solid electrolyte and the negative electrode active material to be well dispersed.

[0390] Regarding the volume ratio "v2:100-v2" of the negative electrode active material and the solid electrolyte contained in the negative electrode 503, 30≤v2≤95 can be satisfied. v2 represents the volume ratio of the negative electrode active material when the total volume of the negative electrode active material and the solid electrolyte contained in the negative electrode 503 is set to 100. When 30≤v2 is satisfied, it is easy to ensure sufficient energy density for the battery 5000. When v2≤95 is satisfied, it is easier for the battery 5000 to work at high output.

[0391] The thickness of the negative electrode 503 may be greater than 10 μm and less than 500 μm. When the thickness of the negative electrode 503 is greater than 10 μm, sufficient energy density can be easily ensured for the battery 5000. When the thickness of the negative electrode 503 is less than 500 μm, the battery 5000 can more easily operate at high output.

[0392] In the case where the negative electrode 503 includes an electrode sheet 401, the thickness of the electrode sheet 401 may be greater than 10 μm and less than 500 μm, or may be greater than 20 μm and less than 200 μm. When the thickness of the electrode sheet 401 is greater than 10 μm, the energy density of the battery 5000 can be increased. When the thickness of the electrode sheet 401 is less than 500 μm, the internal resistance of the battery 5000 is reduced, and operation at high output can be performed. The thickness of the electrode sheet 401 is defined, for example, by the average value of any plurality of points (e.g., 3 points) in a cross section parallel to the thickness direction.

[0393] In order to reduce the interface resistance between each active material and the solid electrolyte, the positive electrode active material and the negative electrode active material may be coated with a coating material. As the coating material, a material with low electronic conductivity may be used. As the coating material, the oxide material, oxide solid electrolyte, halide solid electrolyte, sulfide solid electrolyte, etc. illustrated in Embodiment 2 may be used.

[0394] In order to improve the adhesion between particles, at least one selected from the positive electrode 501, the electrolyte layer 502 and the negative electrode 503 may contain a binder. As the binder, the materials exemplified in Embodiment 1 can be used. In the case where the binder contains an elastomer, there is a tendency to obtain excellent softness and elasticity for each layer of the positive electrode 501, the electrolyte layer 502 and the negative electrode 503 contained in the battery 5000. In this case, the durability of the battery 5000 tends to be improved.

[0395] In order to facilitate the transfer of lithium ions and improve the output characteristics of the battery 5000 , at least one selected from the positive electrode 501 , the electrolyte layer 502 , and the negative electrode 503 may include a non-aqueous electrolyte, a gel electrolyte, or an ionic liquid.

[0396] The non-aqueous electrolyte solution includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, a cyclic carbonate solvent, a chain carbonate solvent, a cyclic ether solvent, a chain ether solvent, a cyclic ester solvent, a chain ester solvent, a fluorine solvent, etc. can be used. As a cyclic carbonate solvent, ethylene carbonate, propylene carbonate, butylene carbonate, etc. can be mentioned. As a chain carbonate solvent, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, etc. can be mentioned. As a cyclic ether solvent, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, etc. can be mentioned. As a chain ether solvent, 1,2-dimethoxyethane, 1,2-diethoxyethane, etc. can be mentioned. As a cyclic ester solvent, γ-butyrolactone, etc. can be mentioned. As a chain ester solvent, methyl acetate, etc. can be mentioned. As the fluorinated solvent, fluoroethylene carbonate, fluoromethyl propionate, fluorobenzene, fluoroethyl methyl carbonate, fluorodimethylene carbonate, etc. can be mentioned. As the non-aqueous solvent, one non-aqueous solvent selected from them can be used alone, or a mixture of two or more non-aqueous solvents selected from them can be used.

[0397] The non-aqueous electrolyte may contain at least one fluorine solvent selected from the group consisting of fluoroethylene carbonate, fluoromethyl propionate, fluorobenzene, fluoroethyl methyl carbonate and fluorodimethylene carbonate.

[0398] As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be cited. As lithium salts, one lithium salt selected from them can be used alone, or a mixture of two or more lithium salts selected from them can be used. The concentration of the lithium salt in the non-aqueous electrolyte can be 0.5 mol / liter or more and 2 mol / liter or less.

[0399] As the gel electrolyte, a material containing a non-aqueous electrolyte in a polymer material can be used. Examples of the polymer material include polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, and polymers having ethylene oxide bonds.

[0400] The cations constituting the ionic liquid include aliphatic chain quaternary cations such as tetraalkylammonium and tetraalkylphosphonium, aliphatic cyclic ammoniums such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium, and piperidinium, and nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium. The anions constituting the ionic liquid may be PF 6- , BF 4- , SbF 6- 、AsF6 - 、SO3CF3 - 、N(SO2F)2- 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - 、C(SO2CF3)3 - etc. The ionic liquid may contain a lithium salt.

[0401] In order to improve electron conductivity, at least one selected from the positive electrode 501 and the negative electrode 503 may contain a conductive auxiliary agent. As the conductive auxiliary agent, the materials exemplified in Embodiment 2 can be used.

[0402] Examples of the shape of the battery 5000 include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, and a laminated shape.

[0403] Example

[0404] The details of the present disclosure are described below using examples and comparative examples. In addition, the solid electrolyte composition, electrode composition, solid electrolyte sheet, electrode sheet, and battery of the present disclosure are not limited to the following examples.

[0405] <Example 1-1>

[0406] [Solvent]

[0407] In all the following steps, a commercially available dehydrated solvent or a solvent dehydrated by nitrogen bubbling was used as the solvent. The water content in the solvent was 10 mass ppm or less.

[0408] [Preparation of adhesive solution]

[0409] In all the following steps, a binder solution is prepared by adding a solvent to a binder to dissolve or disperse the binder in the solvent. The concentration of the binder in the binder solution is adjusted to be 5% by mass or more and 10% by mass or less. Next, a dehydration treatment is performed by nitrogen bubbling until the water content of the binder solution reaches 10 ppm by mass or less.

[0410] In Example 1-1, tetralin was used as the solvent of the adhesive solution. As the adhesive, solution-polymerized styrene butadiene rubber (modified SBR, manufactured by Asahi Kasei Corporation, Asaprene Y031) was used. The molar fraction of the repeating unit derived from styrene in the modified SBR was 0.16. The weight average molecular weight M of the modified SBR was W "Asaprene" is a registered trademark of Asahi Kasei Corporation.

[0411] [Preparation of nitrogen-containing organic solution]

[0412] In all the following steps, when the nitrogen-containing organic matter is a liquid, the nitrogen-containing organic matter is dehydrated by adding molecular sieve 4A 1 / 16. When the nitrogen-containing organic matter is a solid, the nitrogen-containing organic matter is dehydrated by heating at 100° C. for 1 hour in a vacuum atmosphere. A pre-dehydrated solvent is added to the dehydrated nitrogen-containing organic matter to prepare a solution containing the nitrogen-containing organic matter. The concentration of the nitrogen-containing organic matter in the nitrogen-containing organic solution is adjusted to 5% by mass.

[0413] In Example 1-1, tetralin was used as the solvent of the dispersant solution, and 1-hydroxyethyl-2-alkenyl imidazoline (DISPERBYK-109 manufactured by BYK, an aminohydroxy compound containing an alkenyl group having 17 carbon atoms) was used as the nitrogen-containing organic substance.

[0414] [Preparation of Solid Electrolyte Composition]

[0415] In an argon glove box with a dew point of less than -60 ° C, weigh about 12g of Li2S-P2S5 glass ceramics (hereinafter referred to as "LPS"), add tetralin, a solution containing nitrogen-containing organic matter, and a binder solution. The mixing of these materials is carried out in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 5: 0.30, and the solid content concentration of the solid electrolyte composition is adjusted to 45% by mass. Then, a homogenizer (HG-200 manufactured by ASONE) and a generator (K-20S manufactured by ASONE) are used to disperse and mix the obtained mixed solution by shearing. Thus, the solid electrolyte composition of Example 1-1 is obtained.

[0416] In the solid electrolyte composition of Example 1-1, the binder was modified SBR, the nitrogen-containing organic substance was 1-hydroxyethyl-2-alkenyl imidazoline, and the ratio of the mass of the nitrogen-containing organic substance to the mass of the solid electrolyte was 0.30 mass %.

[0417] <Example 1-2>

[0418] The solid electrolyte composition of Example 1-2 was prepared by the same method as Example 1-1, except that these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 5: 0.37. In the solid electrolyte composition of Example 1-2, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.37 mass%.

[0419] <Example 1-3>

[0420] The solid electrolyte composition of Example 1-3 was prepared by the same method as Example 1-1, except that the materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100:5:1.0 when making the solid electrolyte composition. In the solid electrolyte composition of Example 1-3, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass%.

[0421] <Comparative Example 1-1>

[0422] The solid electrolyte composition of Comparative Example 1-1 was prepared by the same method as Example 1-1, except that these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 5: 0.25. In the solid electrolyte composition of Comparative Example 1-1, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.25 mass%.

[0423] <Comparative Example 1-2>

[0424] The solid electrolyte composition of Comparative Example 1-2 was prepared by the same method as Example 1-1, except that an acrylic resin (PMMA, weight average molecular weight 15,000, manufactured by ALDRICH) was used as a binder and these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100:5:0.25. In the solid electrolyte composition of Comparative Example 1-2, the binder is PMMA. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.25% by mass.

[0425] <Comparative Examples 1-3>

[0426] The solid electrolyte composition of Comparative Example 1-3 was prepared by the same method as Example 1-1, except that acrylic resin (PMMA) was used as a binder and these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100:5:1.0. In the solid electrolyte composition of Comparative Example 1-3, the binder is PMMA. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass%.

[0427] <Comparative Examples 1-4>

[0428] The solid electrolyte composition of Comparative Example 1-4 was prepared by the same method as Example 1-1, except that no binder was used and these materials were mixed at a mass ratio of LPS: nitrogen-containing organic matter = 100:1.0. In the solid electrolyte composition of Comparative Example 1-4, no binder was used. The nitrogen-containing organic matter was 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass%.

[0429] <Evaluation of solid electrolyte composition>

[0430] The viscosity ratio of the solid electrolyte compositions of Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-4 was measured by the following method and conditions. In addition, the dispersion stability, viscosity stability, and rheological properties of these solid electrolyte compositions were evaluated.

[0431] [Calculation of viscosity ratio]

[0432] The viscosity of the solid electrolyte composition was measured in a drying room with a dew point of -40°C or less. A viscosity and viscoelasticity measuring device (HAAKE MARS40 manufactured by Thermo Fisher Scientific) and a cone plate with a diameter of 35 mm and an angle of 2° (C35 / 2Ti manufactured by Thermo Fisher Scientific) were used in the measurement. The viscosity of the solid electrolyte composition at a shear rate of 0.1 / sec to 1000 / sec was measured at 25°C and in a speed control mode (CR), and the viscosity ratio η1 / η2 was obtained by the above method.

[0433] [Evaluation of dispersion stability]

[0434] The dispersion stability of the solid electrolyte composition was evaluated in an argon glove box with a dew point below -60°C. 20 ml of the solid electrolyte composition was weighed in a 30 ml glass sample bottle and allowed to stand for 4 days. Then, a medicine spoon was used to visually confirm whether there was a solid deposit (hard cake) at the bottom of the sample tube. In Tables 1 to 5, a circle (○) indicates that there is no solid deposit and the dispersion stability is good. A cross (×) indicates that there is a solid deposit and the dispersion stability is poor.

[0435] [Evaluation of liquidity]

[0436] The fluidity of the solid electrolyte composition is evaluated in a drying room with a dew point below -40°C. A viscosity-viscoelasticity measuring device (manufactured by Thermo Fisher Scientific, HAAKE MARS40) and a cone plate with a diameter of 35 mm and an angle of 2° (manufactured by Thermo Fisher Scientific, C35 / 2Ti) are used in the measurement. Under the conditions of 25°C and speed control mode (CR), the viscosity of the solid electrolyte composition with a shear rate ranging from 0.1 / second to 1000 / second is measured, and the shear rate value is plotted on the horizontal axis and the viscosity value is plotted on the vertical axis to prepare a flow curve. Next, in the prepared flow curve, determine whether the behavior of the solid electrolyte composition is good based on the above-mentioned criteria. In Tables 1 to 5, a circle (○) indicates good fluidity. A cross (×) indicates poor fluidity.

[0437] [Measurement of rheological properties]

[0438] The rheological properties of the solid electrolyte composition were measured in a drying room with a dew point below -40°C. A viscosity and viscoelasticity measuring device (HAAKE MARS40, manufactured by Thermo Fisher Scientific) and a cone plate with a diameter of 35 mm and an angle of 2° (C35 / 2Ti, manufactured by Thermo Fisher Scientific) were used in the measurement. Under the conditions of 25°C and speed control mode (CR), the shear stress of the solid electrolyte composition at a shear rate from 0.1 / sec to 1000 / sec was measured, and the Casson yield value was calculated using the above method. Under the conditions of 25°C, strain control mode (CD), and frequency of 1 Hz, shear was applied to cause the strain (γ) to increase from 0.01% to 10000%. Then, the storage elastic modulus G' and the loss tangent tanδ were measured when γ recovered from 10000% to 0.01%. At this time, the value of the storage elastic modulus G' and the value of the loss tangent tan δ when γ=130% and the value of the storage elastic modulus G' and the value of the loss tangent tan δ when γ=0.1% were obtained.

[0439] The above measurement results are shown in Table 1. The types A and B of the binder and the type a of the nitrogen-containing organic matter in Table 1 correspond to the following contents, respectively.

[0440] A: Modified styrene-butadiene rubber (modified SBR, Asaprene Y031)

[0441] B: Acrylic resin (PMMA)

[0442] a: 1-Hydroxyethyl-2-vinyl imidazoline (manufactured by BYK, DISPERBYK-109)

[0443]

[0444] As shown in Table 1, the solid electrolyte compositions of Examples 1-1 to 1-3 and Comparative Example 1-1 contain modified SBR as a binder. In Examples 1-1 to 1-3 in which the ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte composition is 0.30 mass % or more, solid electrolyte compositions with improved fluidity and dispersion stability are obtained.

[0445] As shown in Table 1, the solid electrolyte compositions of Examples 1-1 to 1-3, Comparative Examples 1-2 and 1-3 contain 1-hydroxyethyl-2-enyl imidazoline as a nitrogen-containing organic matter. In Examples 1-1 to 1-3 using modified SBR as a binder, a solid electrolyte composition with improved fluidity and dispersion stability was obtained. On the other hand, in Comparative Examples 1-2 and 1-3, the dispersion stability of the solid electrolyte composition was poor. It is speculated that the main reason is that PMMA as a binder has poor compatibility with 1-hydroxyethyl-2-enyl imidazoline.

[0446] As shown in Table 1, the solid electrolyte compositions of Examples 1-3 and Comparative Examples 1-4 contain 1-hydroxyethyl-2-alkenyl imidazoline as a nitrogen-containing organic matter. In Examples 1-3 using modified SBR as a binder, a solid electrolyte composition with improved fluidity and dispersion stability is obtained. From these results, it can be inferred that in order to improve the fluidity and dispersion stability of the solid electrolyte composition, it is important to combine a styrene-based elastomer and an aminohydroxy compound.

[0447] <Example 2-1>

[0448] In Example 2-1, tetralin was used as the solvent of the adhesive solution. As the adhesive, solution-polymerized styrene butadiene rubber (modified SBR, manufactured by Asahi Kasei Corporation, Asaprene Y031) was used. The molar fraction of the repeating unit derived from styrene in the modified SBR was 0.16. The weight average molecular weight M of the modified SBR was W It is 380,000.

[0449] In Example 2-1, tetralin was used as the solvent of the dispersant solution, and hexadecylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) which is a primary amine was used as the nitrogen-containing organic substance.

[0450] [Preparation of Solid Electrolyte Composition]

[0451] In an argon glove box with a dew point of less than -60°C, weigh about 14g of LPS, add tetralin, a solution containing nitrogen-containing organic matter, and a solution containing a binder. These materials are mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 3: 1, and the solid content concentration of the solid electrolyte composition is adjusted to 47% by mass. Then, for the obtained mixed solution, a rotation and revolution mixer (made by THINKY, ARE-310) is used to mix in advance, and then an ultrasonic disperser (made by SMT, UH-50) is used to disperse and mix by ultrasonic shearing. Thus, the solid electrolyte composition of Example 2-1 is obtained.

[0452] In the solid electrolyte composition of Example 2-1, the binder was modified SBR, the nitrogen-containing organic substance was hexadecylamine, and the ratio of the mass of the nitrogen-containing organic substance to the mass of the solid electrolyte was 1.0 mass %.

[0453] <Example 2-2>

[0454] The solid electrolyte composition of Example 2-2 was prepared by the same method as Example 2-1 except that coconut amine (manufactured by Kao Corporation, Farmin CS) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 2-2, the binder was modified SBR. The nitrogen-containing organic matter was coconut amine as a primary amine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass%. "Farmin" is a registered trademark of Kao Corporation.

[0455] <Example 2-3>

[0456] The solid electrolyte composition of Example 2-3 was prepared by the same method as Example 2-1 except that N-methyl octadecylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 2-3, the binder is modified SBR. The nitrogen-containing organic matter is N-methyl octadecylamine as a secondary amine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0457] <Example 2-4>

[0458] The solid electrolyte composition of Example 2-4 was prepared by the same method as Example 2-1, except that triethanolamine difatty acid ester (manufactured by BYK, DISPERBYK-108) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 2-4, the binder is modified SBR. The nitrogen-containing organic matter is triethanolamine difatty acid ester as an aminohydroxy compound. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass%.

[0459] <Example 2-5>

[0460] The solid electrolyte composition of Example 2-5 was prepared by the same method as Example 2-1 except that N, N-bis (2-hydroxyethyl) oleylamine (manufactured by Lion Specialty Chemicals, LiponolO / 12) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 2-5, the binder is modified SBR. The nitrogen-containing organic matter is N, N-bis (2-hydroxyethyl) oleylamine as an aminohydroxy compound. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass%.

[0461] <Example 2-6>

[0462] The solid electrolyte composition of Example 2-6 was prepared by the same method as Example 2-1 except that N-tallow alkyl-1,3-diaminopropane (manufactured by Lion Specialty Chemicals, LipominDA-T) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 2-6, the binder is modified SBR. The nitrogen-containing organic matter is N-tallow alkyl-1,3-diaminopropane as a diamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass%.

[0463] <Comparative Example 2-1>

[0464] The solid electrolyte composition of Comparative Example 2-1 was prepared by the same method as Example 2-1 except that N,N-dimethylhexadecylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 2-1, the binder is modified SBR. The nitrogen-containing organic matter is N,N-dimethylhexadecylamine as a tertiary amine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0465] <Comparative Example 2-2>

[0466] The solid electrolyte composition of Comparative Example 2-2 was prepared by the same method as Example 2-1 except that didecylmethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 2-2, the binder is modified SBR. The nitrogen-containing organic matter is didecylmethylamine as a tertiary amine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0467] <Comparative Example 2-3>

[0468] The solid electrolyte composition of Comparative Example 2-3 was prepared by the same method as Example 2-1 except that tri-n-octylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 2-3, the binder is modified SBR. The nitrogen-containing organic matter is tri-n-octylamine as a tertiary amine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0469] <Comparative Example 2-4>

[0470] The solid electrolyte composition of Comparative Example 2-4 was prepared by the same method as Example 2-1 except that stearic acid amide (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 2-4, the binder is modified SBR. The nitrogen-containing organic matter is stearic acid amide as an amide compound. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0471] <Evaluation of solid electrolyte composition>

[0472] For the solid electrolyte compositions of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-4, as an evaluation of dispersion stability, the dispersion stability was evaluated by the same method as in Example 1-1 except that the dispersion was left to stand for 3 days. In addition, for each solid electrolyte composition, the viscosity ratio was calculated by the same method as in Example 1-1. In addition, for each solid electrolyte composition, the rheological properties were evaluated by the same method as in Example 1-1.

[0473] The above measurement results are shown in Table 2. The type A of the binder and the types b to k of the nitrogen-containing organic matter in Table 2 correspond to the following contents, respectively.

[0474] A: Modified styrene-butadiene rubber (modified SBR, Asaprene Y031)

[0475] b: Hexadecylamine (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0476] c: Coconut amine (made by Kao Corporation, Farmin CS)

[0477] d: N-methyloctadecylamine (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0478] e: triethanolamine difatty acid ester (manufactured by BYK, DISPERBYK-108)

[0479] f: N,N-bis(2-hydroxyethyl)oleylamine (manufactured by Lion Specialty Chemicals, Liponol O / 12)

[0480] g: N-tallow alkyl-1,3-diaminopropane (manufactured by Lion Specialty Chemicals, LipominDA-T)

[0481] h: N,N-dimethylhexadecylamine (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0482] i: Didecylmethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0483] j: Tri-n-octylamine (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0484] k: stearic acid amide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0485]

[0486] As shown in Table 2, the solid electrolyte compositions of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-4 contain modified SBR as a binder. In the solid electrolyte compositions of Examples 2-1 to 2-6 containing primary amines, secondary amines, aminohydroxy compounds, or diamines as nitrogen-containing organic substances, solid electrolyte compositions with improved fluidity and dispersion stability were obtained.

[0487] As shown in Table 2, in the solid electrolyte compositions of Example 2-2 and Example 2-4 to Example 2-6, the nitrogen-containing organic matter contains an unsaturated bond. That is, in the solid electrolyte compositions of Example 2-2 and Example 2-4 to Example 2-6, the nitrogen-containing organic matter contains a straight-chain alkenyl group. In the solid electrolyte compositions of Example 2-2 and Example 2-4 to Example 2-6, the storage elastic modulus G' at γ = 0.1% is less than 80 Pa. The solid electrolyte compositions of Example 2-2 and Example 2-4 to Example 2-6 show better fluidity.

[0488] <Example 3-1>

[0489] In Example 3-1, tetralin was used as the solvent of the adhesive solution. As the adhesive, solution-polymerized styrene butadiene rubber (modified SBR, manufactured by Asahi Kasei Corporation, Asaprene Y031) was used. The molar fraction of the repeating unit derived from styrene in the modified SBR was 0.16. The weight average molecular weight M of the modified SBR was w It is 380,000.

[0490] In Example 3-1, tetralin was used as the solvent of the dispersant solution, and 1-hydroxyethyl-2-alkenyl imidazoline (DISPERBYK-109 manufactured by BYK, an aminohydroxy compound containing an alkenyl group having 17 carbon atoms) was used as the nitrogen-containing organic substance.

[0491] [Preparation of Solid Electrolyte Composition]

[0492] In an argon glove box with a dew point of less than -60°C, 14 g of LPS was weighed, tetralin, a solution containing nitrogen-containing organic matter, and a solution containing an adhesive were added. The mixing of these materials was carried out in a mass ratio of LPS: adhesive: nitrogen-containing organic matter = 100: 3: 0.45, and the solid content concentration of the solid electrolyte composition was adjusted to 47% by mass. Then, for the obtained mixed solution, a homogenizer (ASONE, HG-200) and a generator (ASONE, K-20S) were used to disperse and mix by shearing. Thus, the solid electrolyte composition of Example 3-1 was obtained.

[0493] In the solid electrolyte composition of Example 3-1, the binder was modified SBR, the nitrogen-containing organic substance was 1-hydroxyethyl-2-alkenyl imidazoline, and the ratio of the mass of the nitrogen-containing organic substance to the mass of the solid electrolyte was 0.45 mass %.

[0494] <Example 3-2>

[0495] The solid electrolyte composition of Example 3-2 was prepared by the same method as Example 3-1, except that these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 3: 0.70. In the solid electrolyte composition of Example 3-2, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.70 mass%.

[0496] <Example 3-3>

[0497] In addition to using solution polymerized styrene butadiene rubber (SBR, manufactured by Asahi Kasei Corporation, Tufdene 2100R, the molar fraction of the repeating unit derived from styrene is 0.16, the weight average molecular weight M W 390,000) as a binder, the solid electrolyte composition of Example 3-3 was prepared by the same method as Example 3-2. In the solid electrolyte composition of Example 3-3, the binder is SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.70% by mass. "Tufdene" is a registered trademark of Asahi Kasei Corporation.

[0498] <Example 3-4>

[0499] In addition to using a hydrogenated styrene-based thermoplastic elastomer (amine-modified SEBS, manufactured by Asahi Kasei Corporation, Tuftec MP10, with a molar fraction of repeating units derived from styrene of 0.20 and a weight average molecular weight of M WThe solid electrolyte composition of Example 3-4 was prepared by the same method as Example 3-2, except that the solid content concentration of the solid electrolyte composition was adjusted to 56% by mass and the binder was 58,000. In the solid electrolyte composition of Example 3-4, the binder was modified SEBS. The nitrogen-containing organic matter was 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.70% by mass. "Tuftec" is a registered trademark of Asahi Kasei Corporation.

[0500] <Example 3-5>

[0501] In addition to using hydrogenated styrene-based thermoplastic elastomer (SEBS, manufactured by Asahi Kasei Corporation, Tuftec N504, the molar fraction of the repeating unit derived from styrene is 0.21, the weight average molecular weight M W The solid electrolyte composition of Example 3-5 was prepared by the same method as Example 3-2 except that the binder was 230,000. In the solid electrolyte composition of Example 3-5, the binder was SEBS. The nitrogen-containing organic matter was 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.70 mass %.

[0502] <Comparative Example 3-1>

[0503] The solid electrolyte composition of Comparative Example 3-1 was prepared by the same method as Example 3-1, except that these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 3: 0.20. In the solid electrolyte composition of Comparative Example 3-1, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.20 mass%.

[0504] <Comparative Example 3-2>

[0505] The solid electrolyte composition of Comparative Example 3-2 was prepared by the same method as Example 3-3, except that these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 3: 0.20. In the solid electrolyte composition of Comparative Example 3-2, the binder is SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.20 mass%.

[0506] <Comparative Example 3-3>

[0507] The solid electrolyte composition of Comparative Example 3-3 was prepared by the same method as Example 3-4, except that these materials were mixed in a mass ratio of LPS: binder: nitrogen-containing organic matter = 100: 3: 0.20. In the solid electrolyte composition of Comparative Example 3-3, the binder was modified SEBS. The nitrogen-containing organic matter was 1-hydroxyethyl-2-enyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.20 mass%.

[0508] <Comparative Example 3-4>

[0509] The solid electrolyte composition of Comparative Example 3-4 was prepared by the same method as Example 3-2 except that dimethyl palmitamine (manufactured by Kao Corporation, Farmin DM6098) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 3-4, the binder was modified SBR. The nitrogen-containing organic matter was dimethyl palmitamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.70 mass %.

[0510] <Comparative Example 3-5>

[0511] The solid electrolyte composition of Comparative Example 3-5 was prepared by the same method as Example 3-3 except that dimethyl palmitamine (manufactured by Kao Corporation, Farmin DM6098) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 3-5, the binder was SBR. The nitrogen-containing organic matter was dimethyl palmitamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.70 mass %.

[0512] <Comparative Example 3-6>

[0513] The solid electrolyte composition of Comparative Example 3-6 was prepared by the same method as Example 3-4 except that dimethyl palmitamine (manufactured by Kao Corporation, Farmin DM6098) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 3-6, the binder was modified SEBS. The nitrogen-containing organic matter was dimethyl palmitamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.70 mass %.

[0514] <Evaluation of solid electrolyte composition>

[0515] For the solid electrolyte compositions of Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-6, the viscosity ratio was calculated by the same method as in Example 1-1. In addition, for the solid electrolyte compositions of Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-6, the dispersion stability and rheological properties were evaluated.

[0516] The above measurement results are shown in Table 3. The types A to E of the binder and the types a and 1 of the nitrogen-containing organic matter in Table 3 correspond to the following contents, respectively.

[0517] A: Modified styrene-butadiene rubber (modified SBR, Asaprene Y031)

[0518] C: Styrene-butadiene rubber (SBR, Tufdene 2100R)

[0519] D: Modified styrene-ethylene / butylene-styrene block copolymer (amine-modified SEBS, Tuftec MP10)

[0520] E: Styrene-ethylene / butylene-styrene block copolymer (SEBS, Tuftec N504)

[0521] a: 1-Hydroxyethyl-2-vinyl imidazoline (manufactured by BYK, DISPERBYK-109)

[0522] 1: Dimethyl palmitamine (manufactured by Kao Corporation, Farmin DM6098)

[0523]

[0524] As shown in Table 3, the solid electrolyte compositions of Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-6 contain a styrene-based elastomer as a binder. In Examples 3-1 to 3-5, an aminohydroxy compound is used as the nitrogen-containing organic matter, and the ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.30 mass %. In Examples 3-1 to 3-5, a solid electrolyte composition with improved fluidity and dispersion stability is obtained.

[0525] <Example 4-1>

[0526] In Example 4-1, tetralin was used as the solvent of the adhesive solution. As the adhesive, solution-polymerized styrene butadiene rubber (modified SBR, manufactured by Asahi Kasei Corporation, Asaprene Y031) was used. The molar fraction of the repeating unit derived from styrene in the modified SBR was 0.16. The weight average molecular weight M of the modified SBR was W It is 380,000.

[0527] [Preparation of Solid Electrolyte Composition]

[0528] In an argon glove box with a dew point of less than -60°C, tetralin and a binder solution were added to 140 g of LPS. The mixing of these materials was carried out at a mass ratio of LPS: binder = 100: 3, and the solid content concentration of the solid electrolyte composition was adjusted to 51% by mass. Then, the obtained mixed solution was mixed using an online dispersing pulverizer (magicLAB manufactured by IKA). After weighing about 30 g from the obtained mixed solution, 1-hydroxyethyl-2-alkenyl imidazoline (DISPERBYK-109, an aminohydroxy compound containing an alkenyl group having 17 carbon atoms) was added as a nitrogen-containing organic substance at a mass ratio of LPS: nitrogen-containing organic substance = 100: 1.0. Then, the mixed solution was mixed in advance using a rotation and revolution mixer (made by THINKY, ARE-310), and then dispersed and kneaded by high-speed shearing using a homogenizer (made by ASONE, HG-200) and a generator (made by ASONE, K-20S), thereby obtaining the solid electrolyte composition of Example 4-1.

[0529] In the solid electrolyte composition of Example 4-1, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-enyl imidazoline. The mass ratio of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass%. The kneading method after adding the nitrogen-containing organic matter is high shear using a high-speed homogenizer.

[0530] <Example 4-2>

[0531] As a mixing method after adding nitrogen-containing organic matter, an ultrasonic disperser (SMT company, UH-50) was used, and the solid electrolyte composition of Example 4-2 was prepared by the same method as Example 4-1. In the solid electrolyte composition of Example 4-2, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass%. The mixing method after adding the nitrogen-containing organic matter is high shear using an ultrasonic homogenizer.

[0532] <Comparative Example 4-1>

[0533] The solid electrolyte composition of Comparative Example 4-1 was prepared by the same method as Example 4-2, except that these materials were mixed at a mass ratio of LPS: nitrogen-containing organic matter = 100:0.25. In the solid electrolyte composition of Comparative Example 4-1, the binder was modified SBR. The nitrogen-containing organic matter was 1-hydroxyethyl-2-enyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.25 mass%. The mixing method after adding the nitrogen-containing organic matter was high shear using an ultrasonic homogenizer.

[0534] <Evaluation of solid electrolyte composition>

[0535] For the solid electrolyte compositions of Example 4-1, Example 4-2, and Comparative Example 4-1, as an evaluation of dispersion stability, the dispersion stability was evaluated by the same method as in Example 1-1 except that the dispersion was left to stand for 1 day. In addition, for each solid electrolyte composition, the viscosity ratio was calculated by the same method as in Example 1-1. In addition, for each solid electrolyte composition, the rheology was evaluated by the same method as in Example 1-1.

[0536] The above measurement results are shown in Table 4. The type A of the binder and the type a of the nitrogen-containing organic matter in Table 4 correspond to the following contents, respectively.

[0537] A: Modified styrene-butadiene rubber (modified SBR, Asaprene Y031)

[0538] a: 1-Hydroxyethyl-2-vinyl imidazoline (manufactured by BYK, DISPERBYK-109)

[0539]

[0540] As shown in Table 4, the solid electrolyte compositions of Example 4-1, Example 4-2 and Comparative Example 4-1 contain modified SBR and 1-hydroxyethyl-2-alkenyl imidazoline. In Example 4-1 and Example 4-2, in which the ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.30% by mass or more, a solid electrolyte composition with improved fluidity and dispersion stability is obtained. In addition, any of the mixing methods using high shear of a high-speed homogenizer and high shear of an ultrasonic homogenizer can obtain a solid electrolyte composition with improved fluidity and dispersion stability.

[0541] <Example 5-1>

[0542] In Example 5-1, tetralin was used as the solvent of the adhesive solution. As the adhesive, solution-polymerized styrene butadiene rubber (modified SBR, manufactured by Asahi Kasei Corporation, Asaprene Y031) was used. The molar fraction of the repeating unit derived from styrene in the modified SBR was 0.16. The weight average molecular weight M of the modified SBR was W It is 380,000.

[0543] [Preparation of Solid Electrolyte Composition]

[0544] In an argon glove box with a dew point below -60°C, tetralin and a binder solution were added to 210 g of LPS. The materials were mixed in a mass ratio of LPS: binder = 100:3, and the solid content concentration of the solid electrolyte composition was adjusted to 51% by mass. Then, the obtained mixed solution was mixed using an online disperser · grinder (magicLAB, manufactured by IKA). After weighing about 30 g from the obtained mixed solution, hardened tallow alkylamine (LipominHTD, manufactured by Lion Specialty Chemicals) as a nitrogen-containing organic matter was added in a mass ratio of LPS: nitrogen-containing organic matter = 100:1.0, and then an ultrasonic disperser (UH-50, manufactured by SMT) was used to disperse and mix by ultrasonic shearing. Thus, the solid electrolyte composition of Example 5-1 was obtained. "Lipomin" is a registered trademark of Lion Specialty Chemicals.

[0545] In the solid electrolyte composition of Example 5-1, the binder was modified SBR, the nitrogen-containing organic matter was hardened tallow alkylamine, and the ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass %.

[0546] <Example 5-2>

[0547] The solid electrolyte composition of Example 5-2 was prepared by the same method as Example 5-1, except that polyoxyethylene coconut alkylamine (manufactured by Kao Corporation, Amiet102, average addition mole number of ethyleneoxy groups: 2) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 5-2, the binder is modified SBR. The nitrogen-containing organic matter is polyoxyethylene coconut alkylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0548] <Example 5-3>

[0549] The solid electrolyte composition of Example 5-3 was prepared by the same method as Example 5-1, except that 1-hydroxyethyl-2-alkenyl imidazoline (manufactured by Kao Corporation, Homogenol L-95, an alkanolamine compound containing alkenyl groups having 13 to 17 carbon atoms) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 5-3, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0550] <Example 5-4>

[0551] The solid electrolyte composition of Example 5-4 was prepared by the same method as Example 5-1 except that tallow alkylamine (manufactured by Lion Specialty Chemicals, LipominTD) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 5-4, the binder was modified SBR. The nitrogen-containing organic matter was tallow alkylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass %.

[0552] <Example 5-5>

[0553] The solid electrolyte composition of Example 5-5 was prepared by the same method as Example 5-1 except that oleylamine (manufactured by Kao Corporation, Farmin OV) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 5-5, the binder is modified SBR. The nitrogen-containing organic matter is oleylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0554] <Example 5-6>

[0555] The solid electrolyte composition of Example 5-6 was prepared by the same method as Example 5-1, except that 1-hydroxyethyl-2-alkenyl imidazoline (manufactured by BYK, DISPERBYK-109, an aminohydroxy compound containing an alkenyl group having 17 carbon atoms) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Example 5-6, the binder is modified SBR. The nitrogen-containing organic matter is 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0 mass %.

[0556] <Example 5-7>

[0557] In addition to using a hydrogenated styrene-based thermoplastic elastomer (amine-modified SEBS, manufactured by Asahi Kasei Corporation, Tuftec MP10), the molar fraction of the repeating unit derived from styrene is 0.20. The weight average molecular weight M W The solid electrolyte composition of Example 5-7 was prepared by the same method as Example 5-2 except that the solid content concentration was adjusted to 56% by mass and the binder was 58,000. In the solid electrolyte composition of Example 5-7, the binder was modified SEBS. The nitrogen-containing organic matter was polyoxyethylene coconut alkylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0% by mass.

[0558] <Example 5-8>

[0559] The solid electrolyte composition of Example 5-8 was prepared by the same method as Example 5-5, except that a hydrogenated styrene-based thermoplastic elastomer (amine-modified SEBS, manufactured by Asahi Kasei Corporation, Tuftec MP10) was used as a binder and the solid content concentration was adjusted to 56% by mass. In the solid electrolyte composition of Example 5-8, the binder is modified SEBS. The nitrogen-containing organic matter is oleylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 1.0% by mass.

[0560] <Comparative Example 5-1>

[0561] The solid electrolyte composition of Comparative Example 5-1 was prepared by the same method as Example 5-1 except that dimethyl palmitamine (manufactured by Kao Corporation, Farmin DM6098) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 5-1, the binder was modified SBR. The nitrogen-containing organic matter was dimethyl palmitamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass %.

[0562] <Comparative Example 5-2>

[0563] The solid electrolyte composition of Comparative Example 5-2 was prepared by the same method as Example 5-1 except that dimethyltetradecylamine (manufactured by Kao Corporation, Farmin DM4098) was used as the nitrogen-containing organic matter. In the solid electrolyte composition of Comparative Example 5-2, the binder was modified SBR. The nitrogen-containing organic matter was dimethyltetradecylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass %.

[0564] <Determination of iodine value of nitrogen-containing organic matter>

[0565] The iodine value of the nitrogen-containing organic matter used in Example 5-1, Comparative Example 5-1 and Comparative Example 5-2 was measured by the following method. First, a proton nuclear magnetic resonance (NMR) was performed on the sample containing the nitrogen-containing organic matter using a nuclear magnetic resonance device (AVANCE500 manufactured by Bruker). 1 HNMR) measurement. As the measurement sample, a sample in which a nitrogen-containing organic substance is dissolved in heavy chloroform (CDCl3) is used. As the internal standard substance, decamethylcyclopentasiloxane (D5 siloxane) is used. 1 HNMR measurement was performed at a resonance frequency of 500 MHz and room temperature. From the obtained NMR spectrum, the integral value of the peak derived from D5 siloxane and the integral value of the peak derived from the unsaturated bond (C=C skeleton) were calculated. The iodine value (unit: I2 / 100g) of the nitrogen-containing organic matter was calculated using the calculated integral value.

[0566] The iodine value of the nitrogen-containing organic matter used in Examples 5-2 to 5-8 was calculated by the following method: The iodine value (unit: I2 / 100 g) was calculated by the Weiss method using an automatic titrator (AT-710 manufactured by Kyoto Electronics Co., Ltd.) for the measurement sample containing the nitrogen-containing organic matter.

[0567] <Evaluation of solid electrolyte composition>

[0568] For the solid electrolyte compositions of Examples 5-1 to 5-8, Comparative Examples 5-1 and 5-2, as an evaluation of dispersion stability, the dispersion stability was evaluated by the same method as in Example 1-1 except that the dispersion was left to stand for 1 day. In addition, for each solid electrolyte composition, the viscosity ratio was calculated by the same method as in Example 1-1. In addition, for each solid electrolyte composition, the rheology was evaluated by the same method as in Example 1-1.

[0569] The above measurement results are shown in Table 5. The types A and D of the binder and the types a and l to r of the nitrogen-containing organic matter in Table 5 correspond to the following contents, respectively.

[0570] A: Modified styrene-butadiene rubber (modified SBR, Asaprene Y031)

[0571] D: Modified styrene-ethylene / butylene-styrene block copolymer (amine-modified SEBS, Tuftec MP10)

[0572] a: 1-Hydroxyethyl-2-vinyl imidazoline (manufactured by BYK, DISPERBYK-109)

[0573] 1: Dimethyl palmitamine (manufactured by Kao Corporation, Farmin DM6098)

[0574] m: Hardened tallow alkylamine (manufactured by Lion Specialty Chemicals, Lipomin HTD)

[0575] n: Polyoxyethylene coconut alkylamine (made by Kao Corporation, Amiet102)

[0576] o: 1-Hydroxyethyl-2-vinyl imidazoline (manufactured by Kao Corporation, Homogenol L-95)

[0577] p: tallow alkylamine (manufactured by Lion Specialty Chemicals, Lipomin TD)

[0578] q: Oleylamine (manufactured by Kao Corporation, Farmin OV)

[0579] r: dimethyltetradecylamine (manufactured by Kao Corporation, Farmin DM4098)

[0580]

[0581] As shown in Table 5, the solid electrolyte compositions of Examples 5-1 to 5-8, Comparative Examples 5-1 and 5-2 contain modified SBR or amine-modified SEBS. In Examples 5-1 to 5-8, primary amines or aminohydroxy compounds are contained as nitrogen-containing organic substances. In Examples 5-1 to 5-8, solid electrolyte compositions with improved fluidity and dispersion stability are obtained.

[0582] As shown in Table 5, in the solid electrolyte compositions of Examples 5-3 to 5-6 and 5-8, the iodine value of the nitrogen-containing organic matter is greater than 15. In the solid electrolyte compositions of Examples 5-3 to 5-6 and 5-8, the storage elastic modulus G' at γ = 0.1% is less than 80 Pa, and the loss tangent tanδ is greater than 0.4. Therefore, the solid electrolyte compositions of Examples 5-3 to 5-6 and 5-8 show better fluidity.

[0583] <Example 6-1>

[0584] In Example 6-1, tetralin was used as a solvent for the adhesive solution. As an adhesive, a solution-polymerized styrene butadiene rubber (modified SBR, manufactured by Asahi Kasei Corporation, Asaprene Y031) was used. The molar fraction of the repeating unit derived from styrene in the modified SBR was 0.16. The weight average molecular weight M of the modified SBR was W It is 380,000.

[0585] [Preparation of electrode composition]

[0586] In an argon glove box with a dew point below -60°C, 300g of Li(Ni,Co,Al)O2(NCA) coated with LiNbO3 was weighed, 126g of tetralin and 25.2g of a 5% by mass binder solution were added to prepare a mixed solution. For the mixed solution, a desktop digital ultrasonic homogenizer (made by BRANSON, SONIFIER SFX550) was used to disperse and mix. Then, gas-phase carbon fiber (made by Showa Denko, VGCF-H) and acetylene black (made by Denka, DENKABLACKLi, Li-435) were mixed in a mass ratio of gas-phase carbon fiber: acetylene black = 89.5:10.5 to prepare a conductive aid. 8.65g of the conductive aid was added to the mixed solution, dispersed and mixed. Next, 95.0g of LPS was added to the mixed solution, dispersed and mixed. About 40g of the resulting mixed solution was weighed. Furthermore, 1-hydroxyethyl-2-alkenyl imidazoline (DISPERBYK-109 manufactured by BYK, an aminohydroxy compound containing an alkenyl group having 17 carbon atoms) was added to prepare a solution at a mass ratio of LPS: nitrogen-containing organic matter = 100:0.34. The solution was dispersed and kneaded using an ultrasonic disperser (UH-50 manufactured by SMT) to obtain the electrode composition of Example 6-1. "VGCF" is a registered trademark of Showa Denko K.K.

[0587] In the electrode composition of Example 6-1, the binder was modified SBR, the nitrogen-containing organic substance was 1-hydroxyethyl-2-enyl imidazoline, and the ratio of the mass of the nitrogen-containing organic substance to the mass of the solid electrolyte was 0.34 mass %.

[0588] <Example 6-2>

[0589] The electrode composition of Example 6-2 was prepared by the same method as Example 6-1, except that these materials were mixed in a mass ratio of LPS: nitrogen-containing organic matter = 100:1.0. In the electrode composition of Example 6-2, the binder was modified SBR. The nitrogen-containing organic matter was 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass %.

[0590] <Example 6-3>

[0591] The electrode composition of Example 6-3 was prepared by the same method as Example 6-1, except that oleylamine (manufactured by Kao Corporation, Farmin OV) was used as the nitrogen-containing organic matter and these materials were mixed in a mass ratio of LPS: nitrogen-containing organic matter = 100:0.37. In the electrode composition of Example 6-3, the binder is modified SBR. The nitrogen-containing organic matter is oleylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.37 mass%.

[0592] <Example 6-4>

[0593] The electrode composition of Example 6-4 was prepared by the same method as Example 6-1, except that oleylamine (manufactured by Kao Corporation, Farmin OV) was used as the nitrogen-containing organic matter and these materials were mixed at a mass ratio of LPS: nitrogen-containing organic matter = 100:1.0. In the electrode composition of Example 6-4, the binder was modified SBR. The nitrogen-containing organic matter was oleylamine. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 1.0 mass%.

[0594] <Comparative Example 6-1>

[0595] The electrode composition of Comparative Example 6-1 was prepared by the same method as Example 6-1 except that no nitrogen-containing organic matter was used. In the electrode composition of Comparative Example 6-1, the binder was modified SBR. No nitrogen-containing organic matter was used.

[0596] <Evaluation of electrode composition>

[0597] For the electrode compositions of Examples 6-1 to 6-4 and Comparative Example 6-1, as an evaluation of dispersion stability, the dispersion stability was evaluated by the same method as in Example 1-1, except that the mixture was left to stand for 3 days. In addition, for each electrode composition, the viscosity ratio was calculated by the same method as in Example 1-1. Furthermore, for each electrode composition, the rheological properties were evaluated by the same method as in Example 1-1.

[0598] The above measurement results are shown in Table 6. The type A of the binder and the types a and n of the nitrogen-containing organic matter in Table 6 correspond to the following contents, respectively.

[0599] A: Modified styrene-butadiene rubber (modified SBR, Asaprene Y031)

[0600] a: 1-Hydroxyethyl-2-vinyl imidazoline (manufactured by BYK, DISPERBYK-109)

[0601] q: Oleylamine (manufactured by Kao Corporation, Farmin OV)

[0602]

[0603] As shown in Table 6, the electrode compositions of Examples 6-1 to 6-4 and Comparative Example 6-1 contain modified SBR. In Examples 6-1 to 6-4, 1-hydroxyethyl-2-alkenyl imidazoline or oleylamine is contained as the nitrogen-containing organic matter. Thus, in Examples 6-1 to 6-4, electrode compositions with improved fluidity and dispersion stability are obtained.

[0604] <Example 7-1>

[0605] In Example 7-1, tetralin was used as the solvent of the adhesive solution. As the adhesive, solution-polymerized styrene butadiene rubber (modified SBR, manufactured by Asahi Kasei Corporation, Asaprene Y031) was used. The molar fraction of the repeating unit derived from styrene in the modified SBR was 0.16. The weight average molecular weight M of the modified SBR was w It is 380,000.

[0606] In Example 7-1, tetralin was used as the solvent of the dispersant solution, and 1-hydroxyethyl-2-alkenyl imidazoline (DISPERBYK-109 manufactured by BYK, an aminohydroxy compound containing an alkenyl group having 17 carbon atoms) was used as the nitrogen-containing organic substance.

[0607] [Preparation of electrode composition]

[0608] In an argon glove box with a dew point below -60°C, weigh 250 g of Li4Ti5O 12 (LTO), add 136g of tetralin and 15.0g of 5% by mass dispersant solution to prepare a mixed solution. For the mixed solution, a desktop digital ultrasonic homogenizer (made by BRANSON, SONIFIER SFX550) is used to disperse and knead. Then, 43.4g of 5% by mass binder solution, 2.75g of VGCF-H, and 84.0g of LPS are added to the mixed solution and dispersed and kneaded. Then, a rotation and revolution mixer (made by THINKY, ARE-310) is used to disperse and knead the mixed solution to obtain the electrode composition of Example 7-1.

[0609] In the electrode composition of Example 7-1, the binder was modified SBR, the nitrogen-containing organic substance was 1-hydroxyethyl-2-enyl imidazoline, and the ratio of the mass of the nitrogen-containing organic substance to the mass of the solid electrolyte was 0.89 mass %.

[0610] <Comparative Example 7-1>

[0611] The electrode composition of Comparative Example 7-1 was prepared by the same method as Example 7-1 except that an acrylic resin (PMMA, weight average molecular weight of 15,000, manufactured by ALDRICH) was used as a binder. In the electrode composition of Comparative Example 7-1, the binder was PMMA. The nitrogen-containing organic matter was 1-hydroxyethyl-2-alkenyl imidazoline. The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte was 0.89 mass %.

[0612] <Evaluation of electrode composition>

[0613] For the electrode compositions of Example 7-1 and Comparative Example 7-1, as the evaluation of dispersion stability, the dispersion stability was evaluated by the same method as in Example 1-1 except that the dispersion stability was left to stand for 2 days. In addition, for each electrode composition, the viscosity ratio was calculated by the same method as in Example 1-1. Furthermore, for each electrode composition, the rheology was evaluated by the same method as in Example 1-1.

[0614] The above measurement results are shown in Table 7. The types A and B of the binder and the type a of the nitrogen-containing organic matter in Table 7 correspond to the following contents, respectively.

[0615] A: Modified styrene-butadiene rubber (modified SBR, Asaprene Y031)

[0616] B: Acrylic resin (PMMA)

[0617] a: 1-Hydroxyethyl-2-vinyl imidazoline (manufactured by BYK, DISPERBYK-109)

[0618]

[0619] As shown in Table 7, in Example 7-1 and Comparative Example 7-1, 1-hydroxyethyl-2-alkenyl imidazoline was included as the nitrogen-containing organic matter. The electrode composition of Example 7-1 included modified SBR. Thus, in Example 7-1, an electrode composition with improved fluidity and dispersion stability was obtained.

[0620] As shown in Tables 1 to 7, the solid electrolyte composition of the embodiment and the electrode composition of the embodiment have improved fluidity and dispersion stability. The solid electrolyte composition of the embodiment and the electrode composition of the embodiment can manufacture solid electrolyte sheets and electrode sheets in a large area and with high efficiency. That is, the solid electrolyte composition of the embodiment and the electrode composition of the embodiment are suitable for manufacturing large-area and high-efficiency batteries.

[0621] Industrial Availability

[0622] The solid electrolyte composition disclosed herein can be used, for example, in the manufacture of all-solid lithium-ion secondary batteries.

[0623] Description of Reference Numerals

[0624] 101 Solid Electrolyte

[0625] 102 Solvent

[0626] 103 Adhesive

[0627] 104 Nitrogen-containing organic matter

[0628] 111, 121 Ion conductors

[0629] 201 Active substances

[0630] 301 solid electrolyte sheet

[0631] 302 Base Material

[0632] 401, 403 electrode sheet

[0633] 402 Current Collector

[0634] 501 positive electrode

[0635] 502 electrolyte layer

[0636] 503 Negative electrode

[0637] 1000 Solid electrolyte composition

[0638] 2000 Electrode Composition

[0639] 3001 Electrode assembly

[0640] 3002 Transfer Film

[0641] 4001 Electrode

[0642] 4002 Electrode transfer sheet

[0643] 4003 Battery Precursor

[0644] 5000 Battery

Claims

1. A solid electrolyte composition comprising a solvent and an ion conductor, The ion conductor comprises a solid electrolyte, a binder and a nitrogen-containing organic substance, and is dispersed in the solvent. The solid electrolyte comprises a sulfide solid electrolyte, The adhesive comprises a styrene elastomer, The nitrogen-containing organic matter comprises at least one selected from primary amines, secondary amines, aminohydroxy compounds and diamines, The primary amine, the secondary amine, the aminohydroxy compound and the diamine each have at least one selected from a chain alkyl group having 8 or more carbon atoms and a chain alkenyl group having 8 or more carbon atoms, The ratio of the mass of the nitrogen-containing organic matter to the mass of the solid electrolyte is 0.30 mass % or more.

2. The solid electrolyte composition according to claim 1, A ratio η1 / η2 of the viscosity η1 of the solid electrolyte composition measured at 25° C. and a shear rate of 1 / sec to the viscosity η2 of the solid electrolyte composition measured at 25° C. and a shear rate of 100 / sec is 1.4 or more.

3. The solid electrolyte composition according to claim 1, The styrene-based elastomer includes styrene-butadiene rubber.

4. The solid electrolyte composition according to claim 1, The styrene-based elastomer includes at least one selected from the group consisting of modified styrene-butadiene rubber and modified styrene-ethylene / butylene-styrene block copolymer.

5. The solid electrolyte composition according to claim 1, The boiling point of the solvent is 100° C. or higher and 250° C. or lower.

6. The solid electrolyte composition according to claim 1, The solvent contains an aromatic hydrocarbon.

7. The solid electrolyte composition according to claim 6, The solvent comprises tetralin.

8. The solid electrolyte composition according to claim 1, The nitrogen-containing organic compound comprises a straight-chain alkenyl group.

9. The solid electrolyte composition according to claim 8, The nitrogen-containing organic matter comprises oleylamine.

10. The solid electrolyte composition according to claim 1, The iodine value of the nitrogen-containing organic matter is greater than 15.

11. The solid electrolyte composition according to claim 1, The nitrogen-containing organic matter includes the aminohydroxy compound. 12 . An electrode composition comprising the solid electrolyte composition according to claim 1 and an active material.

13. The electrode composition according to claim 12, The nitrogen-containing organic matter includes the aminohydroxy compound.

14. A method for manufacturing a solid electrolyte sheet, comprising: Applying the solid electrolyte composition according to claim 1 on an electrode or a substrate to form a coating film; as well as The solvent is removed from the coating film.

15. A method for manufacturing a battery, comprising the following (i) or (ii): (i) applying the solid electrolyte composition according to claim 1 on the first electrode to form a coating film; removing the solvent from the coating film to form an electrode assembly including the first electrode and the electrolyte layer; and combining the electrode assembly and the second electrode in such a manner that the electrolyte layer is located between the first electrode and the second electrode, (ii) coating the solid electrolyte composition according to claim 1 on a substrate to form a coating film; removing the solvent from the coating film to form the electrolyte layer; and The first electrode, the second electrode, and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode.

16. A method for manufacturing an electrode sheet, comprising: Applying the electrode composition according to claim 12 or 13 on a current collector, a substrate or an electrode assembly to form a coating film; as well as The solvent is removed from the coating film.

17. A method for manufacturing a battery, comprising: a method for manufacturing a battery comprising a first electrode, an electrolyte layer, and a second electrode in this order, comprising the following (iii) or (iv) or (v), (iii) coating the electrode composition according to claim 12 or 13 on a current collector to form a coating film; removing the solvent from the coating film to form the first electrode; and The first electrode, the second electrode and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode, (iv) coating the electrode composition according to claim 12 or 13 on a substrate to form a coating film; removing the solvent from the coating film to form an electrode sheet for the first electrode; and The first electrode, the second electrode and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode, (v) applying the electrode composition according to claim 12 or 13 onto the electrolyte layer of an electrode assembly which is a stack of the first electrode and the electrolyte layer to form a coating film; and The solvent is removed from the coating film to form an electrode sheet for a second electrode.

18. A method for manufacturing a battery, comprising (vi) or (vii), comprising: (vi) coating the electrode composition according to claim 12 or 13 on a current collector to form a first coating film; removing the solvent from the first coating film to form the first electrode; Applying the solid electrolyte composition according to claim 1 on the first electrode to form a second coating film; removing the solvent from the second coating film to form the electrolyte layer; and The first electrode, the electrolyte layer and the second electrode are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode, (vii) coating the electrode composition according to claim 12 or 13 on a first substrate to form a first coating film; removing the solvent from the first coating film to form the first electrode; Applying the solid electrolyte composition according to claim 1 on a second substrate to form a second coating film; removing the solvent from the second coating film to form the electrolyte layer; and The first electrode, the second electrode, and the electrolyte layer are combined in such a manner that the electrolyte layer is located between the first electrode and the second electrode.